A multi-ion competitive exchange model and its solution for leaching ion-absorption rare earth ores - Ping Long; Sihai Luo; Ying Huang; Jie Wang; Fangfang Xie (Minerals Engineering, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Microplastics stimulating polycyclic aromatic hydrocarbon biodegradation via cometabolism in historically coking-contaminated soil: Superior performance of biodegradable microplastics - Guixiang Zhang; Hongyu Zhang; Fengsong Zhang; Lanfang Han; Ke Sun; Hao Wu; Chen Liang; Dandan Liu; Long Ping; Baoshan Xing (Environmental Pollution, 2026)

Bipyridine-based covalent organic framework for trace-level nanofluidic detection of chlorobenzoquinone - Xu-Qin Ran; Xin-Ge Cai; Xiao-Jiao Ren; Xiu-Ping Yan; Hai-Long Qian (Chemical Engineering Journal, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Full motion prediction of a free-fall lifeboat under wind loads using a combined time-domain dynamics and CFD method - Feng Xu; Zhi-Dong Wang; Hong-Jie Ling; Yang-Yue Yan; Peng Dou; Yu-Fei Ding; Ji-Ping Yang; Cai-Long Ren (Ocean Engineering, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Effects of artemisinin on growth, liver structure, lipid metabolism and related gene expression of juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) fed high-lipid diets - Ming-Sheng Xie; Hao Liu; Wei-Bin Huang; Meng-Long Zhou; Wen-Shan Cai; Heng-Yang Song; Shuang Zhang; Bei-Ping Tan; Yuan-Zhi Yang; Xiao-Hui Dong (Animal Feed Science and Technology, 2026)

Natural occurrence of a slow lytic pseudomonas phage in a Pediatric case of multidrug-resistant P. aeruginosa severe pneumonia - Jiaying Sun; Jingru Zhou; Long Wang; Dilare Lidifu; Ping Ni; Qin Li; Xuhua Zhang; Wei Li; Wujin Chen (Virus Genes, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

Structural analysis of wheat endosperm and bran cellulose: Effects on starch gelatinization and gel properties - Ruifeng Ying; Jingyi Zhao; Ping Long; Meigui Huang (Food Hydrocolloids, 2026)

Overcoming mass-transfer bottlenecks in thick electrodes via in-situ growth of high-entropy sulfides on 3D freeze-printed nickel frameworks - Long-Zhe Wei; Yi-Ting Zhang; Hui Sun; Rui-Fen Guo; Ping Shen (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Early Neoproterozoic (∼900 Ma) tectonothermal events in the southwestern Yangtze Block: Evidence from monazite and rutile U-Pb geochronology - Xiao-Ying Cao; Jun-Ping Liu; Shu-Ting Wang; Yu-Chao Wang; Wei Gao; Yan Yang; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

Corrigendum to“Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis” [Insect Biochem. Mol. Biol. 192 (2026) 104578] - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Integrating Clinical Evidence with PBPK Modeling to Assess PPI-Clopidogrel-CYP2C19 Interactions in Chinese ACS Patients - Ya-xin Liu; Yun Kuang; Jun-long Ma; Jin-long Liu; Nuo Xu; Qi Pei; Li-ying Gong; Guo-ping Yang (Pharmaceutical Research, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Multifractal analysis reveals the characterics of soil PSD in the water-level fluctuation zone of the Three Gorges Reservoir, China - Bijie Hu; Zhen Ju; Yuqi Wang; Ping Zhou; Yi Long; Zhonglin Shi (Journal of Soils and Sediments, 2026)

Pose estimation-guided CNN for tea bud detection and plucking point identification - Zhiye Shen; Jiang Yu; Yinghu Cai; Jinpeng Yang; Ping Chen; Weile Ruan; Wenbin Zhen; Ruijun Ma; Long Qi (Computers and Electronics in Agriculture, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

OSL dating of fluvial and lacustrine sediment in Ranwu Lake, Southeastern Tibet - Yang Wu; Yiwei Chen; Long Huang; Ping Ding; Jifeng Zhang; Vladislav S. Isaev; Dmitrii O. Sadokov; Gangjian Wei (Quaternary Geochronology, 2026)

Deciphering auxiliary-driven PFAS profiles among differential textile dyeing processes along source discharge to wastewater treatment and receiving river - Peng Lei; Meng-cheng Wu; Ning Wang; Lei-lei Lu; Guo-dong Kang; Jing-long Liu; Guan-yong Su; Hai-tian Wang; Yan-hua Liu; Sheng-hu Zhang; Ping Wu (Journal of Environmental Chemical Engineering, 2026)

Enhanced lethal effect of UV irradiation on Microcystis aeruginosa assisted by a UV tolerant quorum quenching bacterium: An environmental friendly bloom control strategy - Xiaolei Zhang; Yao Wang; Huihui Chen; Qiang Liu; Ping Yao; Long D. Nghiem (Journal of Environmental Chemical Engineering, 2026)

Exploring relationships between qualitative attributes of urban greenery and soundscape quality assessment: A case study in Singapore - Zuyuan Zhou; Puay Yok Tan; Siu Kit Lau; Xudong Zhang; Sherlyn Xinping Long; Xinyu Chen; Xiao Ping Song (Journal of Environmental Management, 2026)

Taste plasticity and cross-habituation to distinct classes of allelochemicals in the generalist herbivore Spodoptera litura - Dong-Sheng Zhou; Hou-Ding Ou; Xiu-Qin Wang; Ping Zeng; Shi-Mei Wu; Jiu-Mei Long (Journal of Asia-Pacific Entomology, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Metabolic and physiological mechanisms underlying enhanced ε-poly-L-lysine biosynthesis in Streptomyces albulus under ethanol stress - Yi-Hang Chen; Xiao-Yu Wu; Yu Zhou; Xin-Xin Guo; Xu-Sheng Chen; Quan-Ping Liu; Ai-Mei Liao; Yin-Chen Hou; Long Pan (Food Bioscience, 2026)

Cryoprotective effects and mechanisms of heterologously expressed wheat-derived antifreeze peptide on probiotics - Xiaoge Liu; Jingjing Wang; Yingjing Qu; Long Pan; Xin Wang; Kangyi Zhang; Quan-Ping Liu; Na Liu; Jihong Huang; Ai-Mei Liao (Food Bioscience, 2026)

Long-term organic amendments accelerate straw decomposition via specialized microbial enrichment in greenhouse vegetable soils - Long Ma; Shaowen Huang; Dali Song; Chao Ai; Ruonan Li; Liying Wang; Ping He; Wei Zhou (Applied Soil Ecology, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Functional traits are plastic in response to intercropping, improving the stability of yield through temporal asynchrony - Hao Yang; Wei-Ping Zhang; Surigaoge Surigaoge; Hua-Sen Xu; Ye Su; Ragan M. Callaway; Long Li (Field Crops Research, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Recycling high-level liquid waste into covalent organic framework confined unsymmetrical single Pd-N2 site toward H2O2 photosynthesis - Zhi Gao; Ruitao You; Kecheng Pan; Qingsheng Huang; Zhenzhen Xu; Long-Shuai Zhang; Jian-Ping Zou (Resources, Conservation and Recycling, 2026)

MdCNGC15B, a cyclic nucleotide-gated channel (CNGC) protein, positively regulates the tolerance to drought and salt stress in apple - Xin-Long Guo; Hong-Liang Li; Xiang Wu; Tian-tian Wang; Yan-yan Guo; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2026)

Performance assessment of an electrokinetic barrier-aquifer system using a dual-domain solute transport model - Jian-Ping Li; Zhang-Long Chen; Shi-Jin Feng; Wen Zheng; Gang Wang (Journal of Hydrology, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Semi-rational engineering of a β-farnesene synthase hybrid for enhanced production in Serratia marcescens - Wenqi Zhao; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Systems Microbiology and Biomanufacturing, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Sustainable potassium management with green manure reshapes microbial nitrogen cycling to enhance potato yield - Linyirui Ning; Xinpeng Xu; Long Ma; Xiya Wang; Mei Yin; Ping He; Wei Zhou (Agriculture, Ecosystems & Environment, 2026)

The Impact of Delay Time on Blasting Mining Efficiency: Insights from Simulations and Field Experiments - Tao Hu; Xiang-long Li; Jian-guo Wang; Chun-ping Wu; Shu-feng Liang; Bao-qian Huan (Applied Geophysics, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

Tillage combined with straw return increases maize yield and water use by regulating root morphological distribution and nitrogen metabolism in Northeast China - Wen Zhang; Anran Long; Xinjie Ji; Zhanxiang Sun; Ping Tian; Chengcheng Jin; Xiangwei Gong; Ying Jiang; Hua Qi; Haiqiu Yu (Soil and Tillage Research, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

ReaxFF simulation of the degradation mechanism of perfluorononanoic acid (PFNA) by supercritical water oxidation - Hao-Long Su; Guang-Yuan Zhang; Xiao Ma; Yun-Hui Hou; Yuan-Ping Zhang; Hong-Jiang Wang; Jing Sun; Liang Song (Journal of Hazardous Materials, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Metabolic flux balancing and enhanced expression of engineered Paeonia lactiflora pinene synthase for high-yield α-pinene production in Serratia marcescens HBQA7 - Ping Zhang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Bioresource Technology, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

A novel molluscicide: investigating the efficacy of the Penicillium aurantiocandidum Z12 strain in controlling the schistosome-transmitting snail Oncomelania hupensis - Lei Lin; Yin Xiong; Ping Long; Liyun Zhu; Yanfeng Gong; Liang Shi; Xinran Yang; Yue Chen; Qingwu Jiang; Yibiao Zhou (Molluscan Research, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Fate analysis of heavy metals and hydrophobic organic pollutants in tidal flow wetlands: Insights for pollution-specific ecological remediation strategies - Yang Yu; Juan-Ying Li; Si-Xiu Long; Yan-Hong Cai; Bang-Ping Deng; Chun-Yi Zhong; Qian Wang (Marine Environmental Research, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Enhancing free hydroxyl radical generation via noble metal-modified TiO₂ for efficient benzisothiazolinone degradation with reduced H₂O₂ consumption - Meng Xu; Xiao-qing Dong; Li-fang Chen; Ping Yu; Xin-yu Li; Shan-shan Lv; Ya-wen Qi; Wei Zhang; Peng Jiang; Xiao-long Zhou (Journal of Water Process Engineering, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Multigenerational growth inhibition and oxidative stress of polystyrene micro(nano)plastics on earthworms (Eisenia fetida) - Min Li; Fei-Ping Wang; Zi-Qi Chen; Hui Yang; Wan-Ying Zhang; Jie Yang; Hai-Long Liu; Xiao-Zhi Wang; Fei Dang (Environmental Research, 2026)

Using artificial mixtures to test the impacts of tracer combinations and model selection on the performance of sediment source fingerprinting in a burned area - Chen Liang; Zhonglin Shi; Adrian L. Collins; Anbang Wen; Yi Long; Ping Zhou (Environmental Modelling & Software, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Isolation and performance of ultraviolet tolerant bacterium strain for pretreatment and quorum quenching to control reverse osmosis biofouling - Xiaolei Zhang; Jingrui Liu; Shanna Shu; Yingying Qi; Huhui Chen; Qiang Liu; Ping Yao; Long D. Nghiem (Bioresource Technology, 2026)

Causal Relationship Between Galectins With Neuroblastoma: A Mendelian Randomization Study - Chunxi Long; Ping Liang; Xiaoqin Liu; Yali Wang (Molecular Neurobiology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Transgenerational effects of silver nanoparticles in soil to earthworms (Eisenia fetida) - Min Li; Fei-Ping Wang; Hui Yang; Yun-Jie Gan; Hai-Long Liu; Xiao-Zhi Wang (Applied Soil Ecology, 2026)

Preparation of composite material sodium dodecyl sulfonate/2-methylimidazole zinc MOF/ palygorskite and its high- efficiency adsorption for tetracycline - Xin Li; Wen Chen; Jin-Long Jiang; Xia-ping Zhu; Ping Zhao (Applied Clay Science, 2026)

Transient response analysis of saturated-unsaturated subgrade considering pot cover effect - Yun Zhao; Zi-jie Ji; Zhang-long Chen; Dao-sheng Ling; Ping Xu; Zhen-dong Shan (Soil Dynamics and Earthquake Engineering, 2025)

Recultivating abandoned cropland intensifies the trade-off between climate change mitigation and food security within the Yangtze River Basin, China - Yuqiao Long; Jing Sun; Gilles Colinet; Jian Peng; Joost Wellens; Xiuchun Dong; Chuya Wang; Ping Huang; Wenbin Wu; Jeroen Meersmans (Land Use Policy, 2025)

Combined toxicity of cesium and uranium on cyanobacterial growth and metabolism: Mechanisms and implications - Meng-wei Han; Xu Yang; Bin Dong; Jin-long Lai; Hai-ling Xi; San-ping Zhao (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

On-site fluorescent sensing of saccharin using a novel AIE Cd-MOF based on the competitive coordination reaction - Ensheng Zhang; Xianghong Liu; Wenhui Lu; Ping Zhang; Ran Liu; Long Jiang; Ping Ju (Food Chemistry, 2025)

Nicotinamide delays browning in fresh-cut apples through reducing Chlorogenic acid and inhibiting PPO activity - Chen Wang; Lu-Ping Dai; Xin-Ran Bai; Song Zhang; Pei-Qiang Dai; Bao-Long Zhao; Feng-Yun Zhao; Da-Gang Hu (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Boosting (E)-nerolidol yield in Serratia marcescens via nerolidol synthase engineering and competitive pathway knockout - Na Chen; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Food Bioscience, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

Highly selective capture of gold from gold-containing wastewater using ionic network composite membrane - Wan-Ping Huang; Shuang-Long Wang; Bing-Bing Yu; Ya-Shi Chen; Yuan-Hao Wang; Xiao-Lan Yang; Qian Huang; Song Qin; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2025)

Polydopamine-Ag engineered BaTiO₃ core-double-shells nanohybrids in PDMS composites for synergistically enhanced triboelectric output and antibiosis in self-sustaining wearables - Haiyan Fu; Lei Liu; Wei Liu; Zuchang Long; Ping Huang; Kai Fu; Hui Ou; Linmin Hu; Minhao Liao; Jianliang Gong (Chemical Engineering Journal, 2025)

Formation of coastal sand dunes along the northeastern South China Sea revealed by OSL chronology and its interaction with sea level change and human activity - Zibin Fang; Jiewen Xu; Gui Long; Ping Lai; Wen Wang; Ziyuan Wu; Yanwen Li; Wenwen Wu; Xinyi Luo; Yuexin Liu; Hua Tu; Guanjun Xu; et al. (CATENA, 2025)

Molecular and structural insights into neurosporene accumulation in Rhodobacter sphaeroides G1C - Yu-Lu Wu; Guang-Lei Wang; Xiang-Ping Wang; Xing-Yu Yue; Mei-Juan Zou; Zheng-Yu Wang-Otomo; Michael T. Madigan; Richard J. Cogdell; Long-Jiang Yu (Photosynthesis Research, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Exploring the structures and molecular mechanisms of bioactive compounds from marine foods for hyperuricemia prevention: a systematic review - Wenya Meng; Jing Zhang; Hu Hou; Long Yu; Ping Dong (Critical Reviews in Food Science and Nutrition, 2025)

Intercropping enhances soil multifunctionality by restructuring microbial community and biogeochemical cycles - Linkang Chen; Chunyan Ming; Ping Zhao; Pengjie Zhang; Wenchun Yu; Guangqiang Long (Science of The Total Environment, 2025)

Machine learning-driven intelligent screening system for synergistic compound reagent in coal slime flotation - Deke Zhang; Ao Li; Jinyong Li; Yangchao Xia; Budeebazar Avid; Lucai Long; Yuan Ping; Yongchao Piao; Yaowen Xing; Xiahui Gui (Minerals Engineering, 2025)

Synergistic interaction between maillard reaction product and γ-tocopherol in enhancing the oxidation stability of flaxseed oil - Kangyu Zhao; Mengfei Xie; Xin Long; Ping Lan; Zizhe Cai; Yong Wang (Food Research International, 2025)

Multi-omics profiling reveals the dynamic interplay between processing-induced phytochemical transformation and antioxidant bioactivity in ‘Huangkui’ tea (Camellia sinensis) - Zi Wang; Jia-Ping Ke; Gan Chen; Linxin Long; Liang Zhang; Yeyun Li; Zhougao Shen (Food Chemistry, 2025)

Overyielding of maize cultivar mixtures is associated with interaction-driven depth partitioning of roots - Ye Su; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2025)

Numerical modeling of tunnel water inrush in a unified nonlocal general particle dynamics framework - Yu-Long Li; Xiao-Ping Zhou (Engineering Geology, 2025)

Engineering a robust and versatile terpenoid production platform in Serratia marcescens HBQA7 - Long Wang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tian Yang; Tai-Ping Fan; Yujie Cai (Chemical Engineering Journal, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Seismic vulnerability analysis of utility tunnel with oblique incidence of SV waves based on IDA method in horizontal non-homogeneous field - Hui-yue Wang; De-long Huang; Hai-ruo Wang; Yang Ding; Hang Cen; Zi-Yuan Huang; Ai-ping Tang; Xia-xin Tao (Soil Dynamics and Earthquake Engineering, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Effect of dynamic disturbances and dry-wet cycles on the degradation law and acoustic emission evolution characteristics of argillaceous sandstone: An experimental study - Nengzeng Long; Fei Wu; Song Ren; Zheng Chen; Ping Zhang; Chuang Zhang (Journal of Applied Geophysics, 2025)

The nitrogen migration investigation during the pyrolysis and oxidation of C3 amines - Zhi-Hao Zheng; Du Wang; Long Zhao; Jiu-Zhong Yang; Zhan-Dong Wang; Cui-Ping Wang; Zhen-Yu Tian (Fuel, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

A site experiment on the effects of cool coating in a residential community under the tropical climate - Yong Ping Long; E. V. S. Kiran Kumar Donthu; Di Han; Man Di Zhou; Xiao Qin Zhang; Bing Feng Ng; Man Pun Wan (Sustainable Cities and Society, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Molecular mechanisms underlying multi-generational skeletal abnormalities in marine medaka induced by the quinolone antibiotic norfloxacin (NOR) - Cun-Long Wang; Ping Li; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Boronate affinity molecularly imprinted covalent organic framework for highly selective recognition and extraction of zearalenone - Jian Song; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2025)

Storage evolution in non-volatile and volatile lipid oxidation products of salted large yellow croaker based on targeted lipidomics and GC–MS analysis - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Chemistry, 2025)

Nanostructural engineering of cellulose crystals in biomimetic polysaccharide matrix: Deciphering structure-function correlation of hydro-regulatory behavior and its functionalized design for strawberry shelf-life extension - Ruifeng Ying; Ping Long; Meigui Huang (Food Packaging and Shelf Life, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Stiffness matters: Exploiting mechanotransduction to guide cellular behavior and potentiate cancer therapy - Jie Wang; Lin Long; Cheng Sun; Ping Li; Sheng Yao; Ning Wang; Jun Xiao (Chemical Engineering Journal, 2025)

A flexible self-powered multimodal sensor with low-coupling temperature, pressure and humidity detecting for physiological monitoring and human-robot collaboration - Long Ye; Zhenhua Tang; Junshu Feng; Yan-Ping Jiang; Xin-Gui Tang; Yi-Chun Zhou; Xiangjun Xing; Ju Gao (Chemical Engineering Journal, 2025)

Interannual variations in extreme wet spells and their potential causes in Southwest China - Minggang Li; Yong Zhao; Yuan Long; Ping Shao; Yang Li (Atmospheric Research, 2025)

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The R2R3-MYB transcription factor MdMYB62 negatively regulates the drought and salt tolerance in apple - Xin-Long Guo; Xiang Wu; Hong-Liang Li; Ran-Xin Liu; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2025)

Genome-wide identification and expression analysis of RWP-RK genes in Pyropia haitanensis reveals their roles in gametogenesis - Hong‑Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Intercropping enhances stable soil organic carbon pool through macroaggregate protection and biochemical recalcitrance interactions - Ding Wang; Wenchun Yu; Chunyan Ming; Linkang Chen; Ping Zhao; Xiaojun Shi; Zhengxiong Zhao; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2025)

Intercropping enhances the reciprocal facilitation of N and P uptake through complementarity - Hao-Yue Qin; Cheng-Bao Wang; Ping Wang; Si-Cun Yang; Xiao-Fei Li; Long Li (Plant and Soil, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Engineering of farnesyl pyrophosphate hydrolase for farnesol production in Serratia marcescens - Xia Chen; Di Liu; Long Wang; Yao Lu; Yongai Ma; Tai-Ping Fan; Yujie Cai (Systems Microbiology and Biomanufacturing, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Influence of sedimentary environment on rock physical properties of saline lacustrine shale: A case study from the upper member of the Lower Ganchaigou Formation - Hui Xia; Ji-xin Deng; Lian-teng Song; Jian-gong Wang; Ping Zhang; Zhong-hua Liu; Hong-liang Wu; Jia-qing Wang; Yan Long-long (Applied Geophysics, 2025)

Pulmonary arterial hypertension: a long-standing and nonnegligible burden over three decades - Jia-Yong Qiu; Lu-Hong Qiu; Shen-Shen Huang; Bao-Chen Qiu; Chao Liu; Dong Ding; Yue-Jiao Ma; Yu-Ping Zhou; Chun-Yan Cheng; Meng-Yi Liu; Xiao-Wei Gong; Tong-Sheng Wang; et al. (Science Bulletin, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Vertical dynamic response of a pile in three-dimensional saturated soils considering construction disturbance - Chaofan Liu; Zhang-Long Chen; Yun Zhao; Jian-Ping Li; Wei Wang; Jiangtao Yi (Ocean Engineering, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Genesis of strongly peraluminous granites facilitates nitrogen retention in the crust - Yunzhe Chen; Jian Xu; Xiao-Ping Xia; Long Li (Geochimica et Cosmochimica Acta, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Response to sea-level change in a non-deltaic coastal plain: Insights from cores chronologies - Yuexin Liu; Ziyuan Wu; Gui Long; Xinqi Feng; Ping Lai; Zibin Fang; Wenwen Wu; Jiewen Xu; Guanjun Xu; Hua Tu; Hongwei Li; Wen Wang; et al. (Geomorphology, 2025)

Ruthenium-doped molybdenum boride for electrocatalytic hydrogen evolution - Xiang Wang; Panfeng Fan; Yu Xie; Long Zhang; Jiawei Jiang; Ping Huang; Muhammad Ahmad; Yaru Cheng; Jie Zhao (Fuel, 2025)

Microwave thermophysical properties of surface deposits in CE-6 landing region and its potential implications for analyzing the returned samples - Wenqing Chang; Zhiguo Meng; Yi Xu; Xiaoping Zhang; Roberto Bugiolacchi; Long Xiao; Jinsong Ping; Hongbo Zhang; Yuanzhi Zhang (Earth and Planetary Science Letters, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Study on Measurement Method and Influencing Factors of Surface Temperature for Rock Under Microwave Irradiation - Zhongjun Ma; Xiaobao Zhao; Shuo Yang; Yanlong Zheng; Yangwei Long; Ping Che (Rock Mechanics and Rock Engineering, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

GIV/Girdin Modulation of Microglial Activation in Ischemic Stroke: Impact of FTO-Mediated m6A Modification - Peng Xie; Mingyan Xia; Tingting Long; Dongfen Guo; Wenpeng Cao; Ping Sun; Wenfeng Yu (Molecular Neurobiology, 2025)

Identification and evolution characteristics of STAT gene family and the role of STAT1 and STAT3 in trained immunity in largemouth bass (Micropterus salmoides) - Chenyang Yan; Hongzhou Xu; Jingfei Long; Ping Li; Xiaoyu Qi; Yuanjiang Jin; Xiaonan Sun; Haixia Liu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Pepper feeding derivative Brucella sp. in the gut of Spodoptera litura (Lepidoptera: Noctuidae) affect the growth and development of host larvae - Yu Wang; Zhou Yu; Bei-Long Chen; Shao-Shao He; Zi-Yao Liu; Zheng Zhai; Lin Chen; Jiang-Bin Fan; Huan Yu; Zhi-Ping Zuo; Yong-Sheng Zhang (Pesticide Biochemistry and Physiology, 2025)

Data-driven pipeline modeling for predicting unknown protein adulteration in dairy products - Huihui Yang; Yutang Wang; Jinyong Zhao; Ping Li; Zhixiang Li; Long Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2025)

Structural integrity and near-infrared absorption of the LH1 complex of Thermochromatium tepidum: Influence from the C-terminal lysine residues of LH1 α-polypeptide - Yi-Hao Yan; Yu-Qian Li; Mei-Juan Zou; Long-Jiang Yu; Jian-Ping Zhang (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Molecular weight distribution and structure analysis of phlorotannins in Sanhai kelp (Saccharina japonica) and evaluation of their antioxidant activities - Jing Zhang; Long Xing; Wenya Meng; Xiaojie Zhang; Jing Li; Ping Dong (Food Chemistry, 2025)

Hepatoprotective activity of vitamin A and provitamin A purified from scallop (Azumapecten farreri) viscera waste using macroporous resin - Wenya Meng; Xinyi Huang; Long Xing; Jing Zhang; Ping Dong (Food Bioscience, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Skin-like soft yet robust hydrogels with rapid mechanical and electronic responses - Longya Xiao; Yiwan Huang; Sanyu Qian; Shijun Long; Hongjie Jiang; Ping Rao; Xuefeng Li (Chemical Engineering Journal, 2025)

The efficient separation of bioactive components from Eucommia ulmoides Oliver using membrane filtration technology and its mechanisms in preventing alcoholic liver disease - Xiao-Na Le; Da-Ping Long; Shuang-Shuang Yin; Ren-Yan Qing; Zhi-Zheng Chi; Ming-Qing Gao; Ming-Qiang Zhu (Carbohydrate Polymers, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Application of sex-specific markers in identifying the sex of Pyropia haitanensis from different sources - Hong-Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Molecular characteristics of three complete genome sequences of apple rubbery wood virus 1 isolates from apple trees in China - Cheng-long Liu; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Guo-Jun Hu; Ya-Feng Dong (Journal of Plant Pathology, 2025)

Crop diversity significantly enhances soil carbon sequestration via alleviating soil inorganic carbon decline caused by rhizobium inoculation - Chuan-Lin Xiao; Nai-Hao Ji; Ping Wang; Jing-Ru He; Xiang Wang; Long Li (Soil and Tillage Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Anti-inflammatory oxazole-, nitro- and hexahydropyrrolo[2,1-b]oxazole-containing abietane diterpenoid alkaloids from Salvia miltiorrhiza - Li-Xia Wang; Shao-Jie Shi; Li-Ping Long; Xiao-Ping He; Peng Zhang; Xiao-Wen Yang; Yan Liu; Xue-Mei Niu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Intelligent online sensing of lubricating oil debris via dual-electrode oil-driven triboelectric nanogenerator - Long Wang; Jian Yu; Ping Wang; Lei Yang; Xijing Yu; Jianlong Qiu; Kunpeng Tan; Yuanbin Tang; Yanjie Guo (Chemical Engineering Journal, 2025)

Complementarity for nitrogen use in maize/faba bean intercropping with inoculation - Xiao-Fei Li; Ping Wang; Xiu-Li Tian; Nan Dong; Long Li (Plant and Soil, 2025)

Litter functional dissimilarity accelerates carbon and nitrogen release from the decomposition of straw but not root in maize/legume intercropping - Surigaoge Surigaoge; Hao Yang; Dario Fornara; Ye Su; Yu-He Du; Su-Xian Ren; Wei-Ping Zhang; Long Li (Plant and Soil, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Corrigendum: Modelling the bottom-up effects of climate change on primary production in the Gulf of St. Lawrence and eastern Scotian Shelf - Zhi-Ping Mei; Diane Lavoie; Nicolas Lambert; Michel Starr; Joël Chassé; William Perrie; Zhenxia Long (Frontiers in Marine Science, 2024)

Conserved responses of water use to evaporative demand in mixed forest across seasons in low subtropical China - Li-Wei Zhu; Long-Wei Lu; Ping Zhao (Science of The Total Environment, 2024)

Melatonin protects spermatogenic cells against DNA damage and necroptosis induced by atrazine - Tian-Ning Yang; Ning-Ning Huang; Yu-Xiang Wang; Ping-An Jian; Xiang-Yu Ma; Xue-Nan Li; Jin-Long Li (Pesticide Biochemistry and Physiology, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Multigenerational effects of combined exposure of triphenyltin and micro/nanoplastics on marine medaka (Oryzias melastigma): From molecular levels to behavioral response - Jian-Xue Feng; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Cun-Long Wang; Ya-Nan Xu; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Hesperidin and 5, 7-dimethoxycoumarin act as markers in the chemotaxonomy of Citrus medica L. var. sarcodactylis Swingle and Citrus medica L. - Di Wu; Miao-Miao Zhang; Hong-Ping Long; Xiao-Yuan Lin; Kai Liu (Biochemical Systematics and Ecology, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Symbiotrophs dominate rhizosphere soil fungal community stability of the Cathaya argyrophylla - Zhibo Zhou; Peng Xie; Kerui Huang; Ping Mo; Aihua Deng; Shaogang Fan; Binbin Long; Yun Wang (Applied Soil Ecology, 2024)

The Evolution of Microphysical Structures and Cloud-to-Ground Lightning in a Deep Compact Thunderstorm over the Nanjing Area - Ji Yang; Kun Zhao; Ping Song; Long Wen; Fanchao Lyu; Jie Ming; Yuanyuan Zheng (Advances in Atmospheric Sciences, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Alkylglycerol: Not abundant but promising functional lipid - Hai-Long Wang; Chin Ping Tan; Yuanfa Liu; Yong-Jiang Xu (Trends in Food Science & Technology, 2024)

RNAi-mediated silencing of NlGRP3 augments the insecticidal virulence of Metarhizium anisopliae to the brown planthopper Nilaparvata lugens - Zhu-Long Shao; Chen-Ping Lan; Xiao-Ping Yu; Zheng-Liang Wang (Pesticide Biochemistry and Physiology, 2024)

Highly efficient removal and real-time visual detection of fluoride ions using ratiometric CAU-10-NH2@RhB: Probe design, sensing performance, and practical applications - Ping Ju; Wenhui Lu; Guixue Zhang; Shuping Wang; Anzhang Li; Qingxiang Zhang; Long Jiang; Ensheng Zhang; Fengli Qu (Journal of Hazardous Materials, 2024)

Rapid, sensitive, and non-destructive on-site quantitative detection of nanoplastics in aquatic environments using laser-backscattered fiber-embedded optofluidic chip - Yongkai Lu; Tianxiang Ji; Wenjuan Xu; Dan Chen; Ping Gui; Feng Long (Journal of Hazardous Materials, 2024)

Influence of freeze-thaw process on As migration and microorganisms in aggregates of paddy soil - Jinfeng Li; Xiaohui Lu; Ping Wang; Yong Yu; Long Sun; Ming Li (Journal of Environmental Management, 2024)

Galectin-9 activates host immune response and improve immunoprotection of Onychostoma macrolepis against Aeromonas hydrophila infection - Hongzhou Xu; Jingfei Long; Xiaoyu Qi; Ping Li; Chenyang Yan; Lixin Wang; Yuanjiang Jin; Haixia Liu (Fish & Shellfish Immunology, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Recent research progress on recycling metallurgical waste slag and strengthening directional recovery of impurity elements by applied electric field - Wen-zhi Xia; Yun Zhou; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren; Zhi-you Liao; Hai-chuan Wang (Chemical Engineering Journal, 2024)

Responses of soil microbial community diversity and co-occurrence networks to interspecific interactions in soybean/maize and peanut/maize intercropping systems - Huai-Ying Ma; Surigaoge Surigaoge; Yi Xu; Yu-Chen Li; Peter Christie; Wei Ping Zhang; Long Li (Applied Soil Ecology, 2024)

High sulfur-to-iron ratios enhance thallium(I) sequestration by sulfidated zero-valent iron - Nana Wang; Fengli Liu; Huosheng Li; Ping Zhang; Juanxi Huang; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Dan Peng; Yuqi Wang; Huanbin Huang; Zengping Ning (Process Safety and Environmental Protection, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Enhancing the electromagnetic interference shielding performance of composite paper with corrugated paper-like structure - Jiasheng Wei; Ping He; Yantao Yang; Chunxia Tang; Zhu Long; Xiao Chen; Tingzhou Lei; Lei Dai (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Numerical and Field Investigations of Dynamic Failure Caused by Mining-Induced Tremor Based on Focal Mechanism - Zhi-Long He; Yan-Bo Zhang; Cai-Ping Lu; Qi Wang; Xu-Long Yao; Jie-Fang Song; You-Bang Lai (Rock Mechanics and Rock Engineering, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Lime-assisted cultivation of Erigeron breviscapus: enhancing plant biomass production and scutellarin content in cadmium-contaminated soil - Yingpin Liu; Xiu Zhao; Lijie Jia; Yu Chen; Ping Zhao; Shusheng Zhu; Shengchao Yang; Guangqiang Long (Journal of Soils and Sediments, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Highly efficient activation of peroxymonosulfate via KOH-activated Fe@NC for the degradation of bisphenol A - Peng Zhan; Yandong Chai; Wei Sun; Feng-ping Hu; Lanlan Long; Chuqiao Wang; Xiaoming Peng (Environmental Science and Pollution Research, 2024)

From nutrients to fish: Impacts of mesoscale processes in a global CESM-FEISTY eddying ocean model framework - Kristen M. Krumhardt; Matthew C. Long; Colleen M. Petrik; Michael Levy; Frederic S. Castruccio; Keith Lindsay; Lev Romashkov; Anna-Lena Deppenmeier; Rémy Denéchère; Zhuomin Chen; Laura Landrum; Gokhan Danabasoglu; et al. (Progress in Oceanography, 2024)

Characterization of a glycosyltransferase from Paris polyphylla for application in biosynthesis of rare ophiopogonins and ginsenosides - Wen-Ke Xu; Chen-Xiao Zhao; Xiao-Wen Yang; Yue-Gui Chen; Li-Ping Long; Yuan-Feng Yan; Kai Guo; Sheng-Hong Li; Yan Liu (Phytochemistry, 2024)

Co2+ coordination-assisted molecularly imprinted covalent organic framework for selective extraction of ochratoxin A - Li-Hong Su; Hai-Long Qian; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

LC-MS and GC–MS based metabolomics analysis revealed the impact of tea trichomes on the chemical and flavor characteristics of white tea - Xuyang Liu; Feng Zhou; Mingchun Wen; Shan Jiang; Piaopiao Long; Jia-Ping Ke; Zisheng Han; Mengting Zhu; Yu Zhou; Liang Zhang (Food Research International, 2024)

Tuning the planarity of molecularly imprinted covalent organic frameworks for selective extraction of ochratoxin A in alcohol samples - Hao-Ze Li; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Modelling the bottom-up effects of climate change on primary production in the Gulf of St. Lawrence and eastern Scotian Shelf - Zhi-Ping Mei; Diane Lavoie; Nicolas Lambert; Michel Starr; Joël Chassé; William Perrie; Zhenxia Long (Frontiers in Marine Science, 2024)
The Gulf of St. Lawrence (GSL), along with the St. Lawrence Estuary, is the largest estuarine system in North America. It is a biologically productive sea and an important fishing ground in Canada. The objectives of this study are to determine how climate changes will affect primary production in the GSL and on the eastern Scotian Shelf, and to determine the drivers of the changes. We use a regional ocean model forced with downscaled output of the Max-Planck Institute Earth System Model to study the changes in net primary production under the climate change scenario of Representative Concentration Pathway 8.5 (RCP8.5). Results reveal a projected 13.4% decrease in annual primary production across the GSL system over the next 70 years. This decline primarily stems from reduced nutrient concentrations in the upper layer, despite the increase in nutrients supplied by rivers. Enhanced freshwater influx and ocean surface warming contribute to heightened stratification, that in turn reduce the vertical nutrient fluxes from deeper layers. This mechanism affects the upwelling of nutrient-rich water at the head of the Laurentian Channel in the Lower St. Lawrence Estuary, leading to a 22% reduction in the vertical nitrate flux in the future. Additionally, nutrient concentrations in the water masses entering the GSL at the Strait of Belle Isle and at Cabot Strait are also reduced. Due to declining sea-ice concentration, the phytoplankton bloom is expected to occur between 9 and 23 days earlier under a warmer climate, and last for up to 24 days longer, depending on the GSL subregions, compared to the historical period (2001-2020). Biological productivity at higher trophic levels, and thus fisheries productivity, could be negatively impacted under the RCP8.5 climate change scenario.

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

The complete genome sequence of the planctomycetotal bacterium Bremerella sp. P1 with abundant genes involved in polysaccharide degradation - Jia-Xuan Wang; Jing Wang; Ji-Qing Liu; Jian Li; Wen-Xin Jiang; Fei Xu; Ping-Yi Li; Qi-Long Qin; Xiu-Lan Chen; Xi-Ying Zhang (Marine Genomics, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

An insight into trichomes-deficiency and trichomes-rich black teas by comparative metabolomics: The impact of oxidized trichomes on metabolic profiles and infusion color - Piaopiao Long; Shengxiao Su; Mingchun Wen; Xuyang Liu; Zisheng Han; Jia-Ping Ke; Yu Zhou; Mengting Zhu; Yong Cheng; Yundong Shao; Xiaochun Wan; Liang Zhang (Food Research International, 2024)

Decrypting the skeletal toxicity of vertebrates caused by environmental pollutants from an evolutionary perspective: From fish to mammals - Cun-Long Wang; Ping Li; Bin Liu; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Environmental Research, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Biochar modulates intracellular electron transfer for nitrate reduction in denitrifying anaerobic methane oxidizing archaea - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Simplified Calculation of Earthquake Energy Transfer of Different Pipe Supports Inside Utility Tunnel at Horizontal Non-Homogeneous Field - De-long Huang; Hang Cen; Jin Wang; Hui-yue Wang; Qiang Liu; Zhong-ling Zong; Ai-ping Tang; Song-ling Xue (Geotechnical and Geological Engineering, 2024)

Investigation of the mutual crosstalk between ER stress and PI3K/AKT/mTOR signaling pathway in iron overload-induced liver injury in chicks - Xiang-Long Lv; Wen-Lei Li; Feng-Jiao Sun; Yu-Zhi An; Ning Sun; Xiao-Ping Lv; Xue-Li Gao (BioMetals, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Engineering of molecularly imprinted cavity within 3D covalent organic frameworks: An innovation for enhanced extraction and removal of microcystins - Yu-Hong Tang; Tian-Tian Ma; Xu-Qin Ran; Yukun Yang; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Comparative plastomes of eight subgenus Chamaesyce plants and system authentication of Euphorbiae Humifusae Herba - Long Wang; Ziting Huo; Wenbo Xu; Peina Zhou; Wenxiang Nan; Huijun Guo; Qianwen Zhang; Peng Yang; Raphael N. Alolga; Xiaojian Yin; Ping Li; Xu Lu (Food Chemistry, 2024)

Study of the dynamic interactions between helix-stiffened cement mixing piles and soft soil under oblique incidence of SV waves in arbitrary space - Hang Cen; Zhong-ling Zong; De-long Huang; Hui-yue Wang; Xiao-xuan Zhuang; Zi-yuan Huang; Ai-ping Tang (Computers and Geotechnics, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Novel Programmed Death Ligand 1-AKT-engineered Mesenchymal Stem Cells Promote Neuroplasticity to Target Stroke Therapy - Syuan-Ling Lin; Wei Lee; Shih-Ping Liu; Yi-Wen Chang; Long-Bin Jeng; Woei-Cherng Shyu (Molecular Neurobiology, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Study on the thermal behaviour of spontaneous combustion of open-pit minerals - Jing-Yu Zhao; Zhao-Long Chi; Jia-Jia Song; Shi-Ping Lu; Yan-Ni Zhang; Chang-Kui Lei; Chi-Min Shu (Science of The Total Environment, 2024)

Fluvial landscape change in Anqing through the last glacial cycle: Implications for eustatic controls on the Yangtze River's continental-scale incision-aggradation cycles - Xiaowen Wu; Lei Wang; La Ta; Changhui Guo; Long Qiao; Huiying Wang; Ping Wang; Liubing Xu; Jinming Xie; Jiafu Zhang; Xin Wang; Chunxin Wang; et al. (Quaternary Science Reviews, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Correlations of dynamic changes in lipid and protein of salted large yellow croaker during storage - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Research International, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Simulation advances with EnviBatE- A case study on urban heat island mitigation in Singapore - E.V.S. Kiran Kumar Donthu; Georgios-E Kyriakodis; Xiaoqin Zhang; Yong Ping Long; Man Pun Wan; Emmanuel Bozonnet (Building and Environment, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Microbial mechanisms of C/N/S geochemical cycling during low-water-level sediment remediation in urban rivers - Wen-Long Chen; Min Zhang; Jian-Guo Wang; Wei-Jie Huang; Qiong Wu; Xiao-Ping Zhu; Ning Li; Qian Wu; Wei Guo; Jun Chen (Journal of Environmental Management, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Coupling raw material cultivation with nano-hydroxyapatite application to utilize and remediate severely Cd-containing soil - Lijie Jia; Yanli Zhou; Yunxia Su; Ping Zhao; Jingling Zhang; Wei Fan; Shengchao Yang; Guangqiang Long (Process Safety and Environmental Protection, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Integrating molecular imprinting into flexible covalent organic frameworks for selective recognition and efficient extraction of aflatoxins - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

The effect of triclosan on intergeneric horizontal transmission of plasmid-mediated tigecycline resistance gene tet(X4) from Citrobacter freundii isolated from grass carp gut - Xinxin Jiang; Jingfei Long; Yanzhen Song; Xiaoyu Qi; Ping Li; Kuiquan Pan; Chenyang Yan; Hongzhou Xu; Haixia Liu (Environmental Pollution, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Dynamics of cool surface performance on urban microclimate: A full-scale experimental study in Singapore - E. V. S. Kiran Kumar Donthu; Yong Ping Long; Man Pun Wan; Mandi Zhou; Bing Feng Ng (Sustainable Cities and Society, 2024)

Efficient perchlorate reduction in microaerobic environment facilitated by partner methane oxidizers - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Journal of Hazardous Materials, 2024)

First magnetic and spectroscopic constraints on attenuated space weathering at the Chang'e-5 landing site - Yuqi Qian; Long Xiao; Jiawei Zhao; James W. Head; Qi He; Huiru Xu; Feizhou Wang; Xiaoping Zhang; Xianquan Ping; Wen Zeng; Xing Wang; Joseph Michalski; et al. (Icarus, 2024)

Temporal dynamics of plant−soil feedback and related mechanisms depend on environmental context during invasion processes of a subtropical invader - Yang-Ping Li; Wei-Tao Li; Ju Li; Yu-Long Feng (Plant and Soil, 2024)

Understanding District Heating Networks Vulnerability: A Comprehensive Analytical Approach with Controllability Consideration - Ding Mao; Peng Wang; Yi-Ping Fang; Long Ni (Sustainable Cities and Society, 2024)

Long-term tralopyril exposure results in endocrinological and transgenerational toxicity: A two-generation study of marine medaka (Oryzias melastigma) - Bin Liu; Ping Li; Ren-Yan Du; Cun-Long Wang; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

Catalytic reforming of cellulose pyrolysis volatiles over hierarchical HZSM-5: Mechanism of a protective effect of tetrapropylammonium (TPA+) during alkali treatment - Xin-Bo Pang; Jing-Pei Cao; Nai-Yu Yao; Jing-Ping Zhao; Tian-Long Liu; Shi-Jie Cai; Hong-Yan Wang; Yan-Cheng Hu; Xiao-Yan Zhao (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Pretreatment by a novel photo-electro reactor to control organic and biofouling during reverse osmosis filtration of reclaimed water - Xiaolei Zhang; Hanyue Zheng; Zhiquan Wang; Yangzhou Su; Huihui Chen; Qiang Liu; Ping Yao; Naresh Mameda; Hao H. Ngo; Long D. Nghiem (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Oral Administration of the Antimicrobial Peptide Mastoparan X Alleviates Enterohemorrhagic Escherichia coli–Induced Intestinal Inflammation and Regulates the Gut Microbiota - Xue Qin Zhao; Lei Wang; Chun Ling Zhu; Xiang Hong Xue; Xiao Jing Xia; Xi Long Wu; Yun Di Wu; Shan Qin Liu; Gai Ping Zhang; Yue Yu Bai; Hanna Fotina; Jian He Hu (Probiotics and Antimicrobial Proteins, 2024)

Responses of carbon and microbial community structure to soil nitrogen status vary between maize and potato residue decomposition - Linkang Chen; Ping Zhao; Chunyan Ming; Wenchun Yu; Rui Xiang; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Co-catalytic of aluminosilicate stabilized cobalt for peroxymonosulfate activation to degrade levofloxacin - Manlu Cheng; Xingyu Long; Ping Song; Zenghui Diao; Gang Song; Diyun Chen; Lingjun Kong (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Microbial stratification protects denitrifying anaerobic methane oxidation archaea and bacteria from external oxygen shock in membrane biofilm reactor - Pan-Long Lv; Chuan Jia; Xu Guo; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Identification, Evolutionary Relationship Analysis of the Trehalose-6-Phosphate Synthase (TPS) Gene Family in Common Bean (Phaseolus vulgaris) and Their Expression in Response to Cold Stress - Wei Liu; Huan-Huan Zhang; Zi-Xuan Long; Xiao-Na Chi; Yu-Ping Wang (Journal of Plant Growth Regulation, 2024)

The phosphoproteome is a first responder in tiered cellular adaptation to chemical stress followed by proteomics and transcriptomics alteration - Peiru Chen; Yuan Li; Qi Long; Tao Zuo; Zhenpeng Zhang; Jiabin Guo; Danyang Xu; Kaixuan Li; Shu Liu; Suzhen Li; Jian Yin; Lei Chang; et al. (Chemosphere, 2023)

Topological and functional vulnerability analysis and mitigation for single-source heating networks based on tree models - Ding Mao; Peng Wang; Yi-Ping Fang; Long Ni (Sustainable Cities and Society, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Lipidomics reveals the relationship between lipid oxidation and flavor formation of basic amnio acids participated Low-Sodium cured large yellow croaker - Min Zhang; Jing-Jing Fu; Jun-Long Mao; Xiu-Ping Dong; Yue-Wen Chen (Food Chemistry, 2023)

Analytical solution for contaminant transport through a GCL-enhanced composite cutoff wall system - Jun Liu; Zhang-Long Chen; Chuang Yu; Shun Wang; Wei Wu; Shi-Ping Xie (Computers and Geotechnics, 2023)

Ti3C2Tx quantum dot-modified Ti3C2Tx nanosheets freestanding films for flexible solid-state pseudocapacitors - Ping Liu; Handan Liu; Tengfei Zhang; Long Chen; Wen Guo; Tiantian Gu; Feng Yu; Yanyan Liu; Gang Wang (Chemical Engineering Journal, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Comparative transcriptome analysis reveals candidate genes related to the sex differentiation of Schisandra chinensis - Ji-Long Cheng; Xue-Ping Wei; Yu Chen; Yao-Dong Qi; Ben-Gang Zhang; Hai-Tao Liu (Functional & Integrative Genomics, 2023)

Divergent seasonal patterns and drivers of soil respiration in alpine forests of northwestern China - Long-Fei Chen; Shu-Ping Yang; Zhi-Bin He; Wen-Zhi Zhao; Jun-Qia Kong; Xiang-Yan Feng; Xiao-Gang Li (Agricultural and Forest Meteorology, 2023)

New benzofuran neolignans with neuroprotective activity from Phyllanthodendron breynioides - Tong Su; Mei-Cen Pu; Di-Kai Tang; Jin-Chen Long; Fang-Yu Yuan; Ai-Ping Yin; Shu-Qi Wu; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Biomass-derived carbon dots with light conversion and nutrient provisioning capabilities facilitate plant photosynthesis - Bingxu Cheng; Zhilin Yang; Feiran Chen; Le Yue; Xuesong Cao; Jing Li; Hai-Long Qian; Xiu-Ping Yan; Chuanxi Wang; Zhenyu Wang (Science of The Total Environment, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

Oxygen-insensitive nitroreductase bacteria-mediated degradation of TNT and proteomic analysis - Mao-ling Yin; San-ping Zhao; Jin-long Lai; Xu Yang; Bin Dong; Yong-bing Zhu; Yu Zhang (Environmental Science and Pollution Research, 2023)

The long-term effects of thinning on soil respiration vary with season in subalpine spruce plantations - Long-Fei Chen; Zhi-Bin He; Wen-Zhi Zhao; Lei Ma; Sheng-En Liu; Li-Wen Zhao; Shu-Ping Yang; Xiang-Yan Feng (Agricultural and Forest Meteorology, 2023)

A new species of Coccoglypta Pilsbry, 1895 from China (Gastropoda, Camaenidae) - Zhong-Guang Chen; Guang-Long Xie; Yu-Ting Dai; Shan Ouyang; Xiao-Ping Wu (Molluscan Research, 2023)

16-Hydroxybriaranes from the octocoral Briareum stechei - Chia-Jung Liu; Chien-Chiao Wang; Chun-Feng Chang; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Tsong-Long Hwang; You-Ying Chen; Ping-Jyun Sung (Phytochemistry Letters, 2023)

Investigation on the flow characteristics near the duct of a pump-jet propulsion under different advance coefficient conditions - Shun Xu; Yong-liang Xiong; Gui-bin Li; Ming-yuan Wei; Xin-ping Long; Bin Ji (Ocean Engineering, 2023)

Phosphoproteome reveals long-term potentiation deficit following treatment of ultra-low dose soman exposure in mice - Qi Long; Zhenpeng Zhang; Yuan Li; Yuxu Zhong; Hongyan Liu; Lei Chang; Ying Ying; Tao Zuo; Yong'an Wang; Ping Xu (Journal of Hazardous Materials, 2023)

Surface imprinted-covalent organic frameworks for efficient solid-phase extraction of fluoroquinolones in food samples - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2023)

Synergistic extraction of valuable metals from cyanide tailings slurry electrolyte and preparation of ferrous oxalate - Yonghui Song; Jin Bao; Long Liao; Ping Dong; Yifan Wang; Xinwei Zhang (Journal of Environmental Chemical Engineering, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Reduction and adsorption of uranium(VI) from aqueous solutions using nanoscale zero-valent manganese - Xiaohan Li; Juanxi Huang; Zhengqin Shi; Yuan Xie; Zhengfan Xu; Jianyou Long; Gang Song; Yaxuan Wang; Gaosheng Zhang; Xiatiao Luo; Ping Zhang; Shuxiang Zha; et al. (Journal of Environmental Management, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

Irreversible fluorine covalent organic framework based probe nanoelectrospray ionization mass spectrometry for direct and rapid determination of perfluoroalkyl carboxylic acids - Xu-Qin Ran; Shu-Ting Xu; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2023)

The innovative and accurate detection of heavy metals in foods: A critical review on electrochemical sensors - Ruonan Meng; Qiujin Zhu; Tingyu Long; Xuli He; Zewei Luo; Ronghui Gu; Wenzhong Wang; Ping Xiang (Food Control, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Contamination characteristics and source analysis of potentially toxic elements in dustfall-soil-crop systems near non-ferrous mining areas of Yunnan, southwestern China - Ying Luo; Zhe Wang; Zhen-Long Zhang; Jia-Qian Zhang; Qiu-Ping Zeng; Duan Tian; Chao Li; Feng-Yu Huang; Shu Chen; Li Chen (Science of The Total Environment, 2023)

Attapulgite amendment favors the utilization of high cadmium-contaminated soil for Erigeron breviscapus cultivation - Lijie Jia; Wei Fan; Peili Wang; Yu Chen; Ping Zhao; Shengchao Yang; Guangqiang Long (Chemosphere, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes - Jing Li; Yu-Fen Tan; Si-Qian Zhou; Shao Liu; Wen-Xuan Wang; Yue-Ping Jiang; Hong-Ping Long; Ji-Kai Liu (Phytochemistry, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Enhancing solid-like characteristics of porcine plasma protein-carrageenan-based high internal phase emulsion: As solid fat alternative of loading curcumin - Jianglan Yuan; Ping Yan; Xiaocui Liu; Xu Kang; Yongguo Jin; Long Sheng; Jianxin Xia (Food Hydrocolloids, 2023)

Reduced and deep application of controlled-release urea maintained yield and improved nitrogen-use efficiency - Kaibo Hu; Ping Zhao; Kaixian Wu; Hongli Yang; Qingxia Yang; Maopan Fan; Guangqiang Long (Field Crops Research, 2023)

A genome-wide co-expression network analysis revealed ZmNRAMP6-mediated regulatory pathway involved in maize tolerance to lead stress - Peng Liu; Li Jiang; Ping Long; Qinglin Li; Fengxia Hou; Guangsheng Yuan; Zhong Chen; Minyan Zhang; Chaoying Zou; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Thallium removal from wastewater using sulfidized zero-valent manganese: Effects of sulfidation method and liquid nitrogen pretreatment - Zhengqin Shi; Ping Zhang; Xiaohan Li; Yijie Zheng; Juanxi Huang; Yaxuan Wang; Xiatiao Luo; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Huosheng Li (Chemosphere, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Specific activation of cGAS-STING pathway by nanotherapeutics-mediated ferroptosis evoked endogenous signaling for boosting systemic tumor immunotherapy - Jun-Long Liang; Xiao-Kang Jin; Shi-Man Zhang; Qian-Xiao Huang; Ping Ji; Xin-Chen Deng; Si-Xue Cheng; Wei-Hai Chen; Xian-Zheng Zhang (Science Bulletin, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Development of a Nafion-MWCNTs and in-situ generated Au nanopopcorns dual-amplification electrochemical aptasensor for ultrasensitive detection of OTA - Yujiao Hou; Nan Long; Qingbin Xu; Ying Li; Pengyue Song; Minghan Yang; Jiabo Wang; Lidong Zhou; Ping Sheng; Weijun Kong (Food Chemistry, 2023)

Dual seasonal pattern for hemorrhagic fever with renal syndrome and its potential determinants in China - Chen-Long Lv; Yao Tian; Yan Qiu; Qiang Xu; Jin-Jin Chen; Bao-Gui Jiang; Zhong-Jie Li; Li-Ping Wang; Simon I. Hay; Wei Liu; Li-Qun Fang (Science of The Total Environment, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Unveiling the enhancement essence on Li2S deposition by the polarized topological β-polyvinylidene fluoride: Beyond built-in electric field effect - Guo Wen Sun; Meng Jing Jin; Qian Yu Liu; Chao Yue Zhang; Jiang Long Pan; Yan Chun Wang; Xiu Ping Gao; Geng Zhi Sun; Xiao Jun Pan; Jin Yuan Zhou (Chemical Engineering Journal, 2023)

Export of Greenland Sea water across the Mohn Ridge induced by summer storms - Xusiyang Shen; Jinping Zhao; Xiaoyu Wang; Tore Hattermann; Wenqi Shi; Long Lin; Ping Chen (Acta Oceanologica Sinica, 2023)

Disruption of tetrahydrobiopterin (BH4) biosynthesis pathway affects cuticle pigmentation in Henosepilachna vigintioctopunctata - Long-Ji Ze; Ping Xu; Jian-Jian Wu; Lin Jin; Ahmad Ali Anjum; Guo-Qing Li (Journal of Insect Physiology, 2023)

Enhanced stability and combustion performance of AlH3 in combination with commonly used oxidizers - Ming-Hui Yu; Su-Lan Yang; Wu-Xi Xie; Zhao-Yang Zhu; He-Ping Li; Qi-Long Yan (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Dysfunction of DNA repair for boosted tumor cell cycle arrest based on NIR-II biodegradable Te-prussian blue nanorod - Xiaoyang Liang; Ping Liu; Wen Li; Long Binh Vong; Tingting Wang; Lujing Geng; Yue Zhou; Siyu Wang; Qiang Lu; Fengping Tan; Xinxing Wang; Nan Li (Chemical Engineering Journal, 2023)

Silencing circ_0074371 inhibits the progression of sepsis-induced acute kidney injury by regulating miR-330-5p/ELK1 axis - Qiu-yuan Wang; Rong-rong Zhang; Long Cui; Ya-ping Sun (Mammalian Genome, 2022)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

Computational Study of Methionine Methylation Process Catalyzed by SETD3 - Yuan-Yuan Zhao; Hao Deng; Adua Rahman; Xiao-Long Xu; Ping Qian; Hong Guo (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Ecosystem Mercury Recovery and Health Benefit Under the Minamata Convention in a Changing Climate - Qingru Wu; Yanxu Zhang; Ping Li; Xuewu Fu; Qianggong Zhang; Xun Wang; Long Chen; Shuxiao Wang; Feiyue Wang; Xinbin Feng (Reviews of Environmental Contamination and Toxicology, 2022)

Ground validation of Fengyun-4A and Global Precipitation Measurement satellite observations over an alpine and canyon basin of the southeastern Tibetan Plateau - Yin-ping Long; Gong-yan Chen; Qin-min Ma; Jun Chen (Journal of Mountain Science, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Numerical and Field Investigations of Rockburst Mechanisms Triggered by Thick-Hard Roof Fracturing - Zhi-Long He; Cai-Ping Lu; Xiu-Feng Zhang; Ying Guo; Zhao-He Meng; Lei Xia (Rock Mechanics and Rock Engineering, 2022)

A1 Adenosine Receptor Activation Inhibits P2X3 Receptor–Mediated ATP Currents in Rat Dorsal Root Ganglion Neurons - Jia-Wei Hao; Wen-Long Qiao; Qing Li; Shuang Wei; Xue-Mei Li; Ting-Ting Liu; Chun-Yu Qiu; Wang-Ping Hu (Molecular Neurobiology, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Sulfur fertiliser enhancement of Erigeron breviscapus (Asteraceae) quality by improving plant physiological responses and reducing soil cadmium bioavailability - Yonglin Liu; Yingpin Liu; Yu Chen; Ping Zhao; Shengchao Yang; Shuran He; Guangqiang Long (Environmental Science and Pollution Research, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Testing environmental Kuznets curve hypothesis: considering the impact of Sino-US trade on three main industries in China - Long-kang Wu; Tian-tian Feng; Hui Luo; Xiao-lei Gong; Jian-ping Ge (Environmental Science and Pollution Research, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

miR171 modulates induction of somatic embryogenesis in citrus callus - Qiao-Fang Shi; Jian-Mei Long; Zhao-Ping Yin; Nan Jiang; Meng-Qi Feng; Bo Zheng; Wen-Wu Guo; Xiao-Meng Wu (Plant Cell Reports, 2022)

Prognostic Value of miR-137 in Children with Medulloblastoma and its Regulatory Effect on Tumor Progression - Wenyuan Ji; Xuan Zhe; Lusheng Li; Yang Cheng; Xueling Zhao; Ping Liang; Chunxi Long; Jianjun Zhou (NeuroMolecular Medicine, 2022)

Episodic Neoproterozoic extension-related magmatism in the Altyn Tagh, NW China: implications for extension and breakup processes of Rodinia supercontinent - Jiang-bo Hao; Chao Wang; Ji-heng Zhang; Liang Liu; Yong-sheng Gai; Hang Li; Zun-pu Yu; Joseph G Meert; Xiao-ping Long; Xiao-kui Sun; Shuai Zhang (International Geology Review, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Approximate analytical solution for seepage field of drained tunnel in vertically stratified phreatic aquifer - Wei Meng; Chuan He; Fang-yin Wu; Wen-bo Yang; Hao Kou; Zi-han Zhou; De-ping Guo; Hai-long Meng (Journal of Mountain Science, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Targeting GATA1 and p2x7r Locus Binding in Spinal Astrocytes Suppresses Chronic Visceral Pain by Promoting DNA Demethylation - Yan-Yan Wu; Hai-Long Zhang; Xiaomin Lu; Han Du; Yong-Chang Li; Ping-An Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2022)
Irritable bowel syndrome is a gastrointestinal disorder of unknown etiology characterized by widespread, chronic abdominal pain associated with altered bowel movements. Increasing amounts of evidence indicate that injury and inflammation during the neonatal period have long-term effects on tissue structure and function in the adult that may predispose to gastrointestinal diseases. In this study we aimed to investigate how the epigenetic regulation of DNA demethylation of the p2x7r locus guided by the transcription factor GATA binding protein 1 (GATA1) in spinal astrocytes affects chronic visceral pain in adult rats with neonatal colonic inflammation (NCI). The spinal GATA1 targeting to DNA demethylation of p2x7r locus in these rats was assessed by assessing GATA1 function with luciferase assay, chromatin immunoprecipitation, patch clamp, and interference in vitro and in vivo . In addition, a decoy oligodeoxynucleotide was designed and applied to determine the influence of GATA1 on the DNA methylation of a p2x7r CpG island. We showed that NCI caused the induction of GATA1, Ten-eleven translocation 3 (TET3), and purinergic receptors (P2X7Rs) in astrocytes of the spinal dorsal horn, and demonstrated that inhibiting these molecules markedly increased the pain threshold, inhibited the activation of astrocytes, and decreased the spinal sEPSC frequency. NCI also markedly demethylated the p2x7r locus in a manner dependent on the enhancement of both a GATA1–TET3 physical interaction and GATA1 binding at the p2x7r promoter. Importantly, we showed that demethylation of the p2x7r locus (and the attendant increase in P2X7R expression) was reversed upon knockdown of GATA1 or TET3 expression, and demonstrated that a decoy oligodeoxynucleotide that selectively blocked the GATA1 binding site increased the methylation of a CpG island in the p2x7r promoter. These results demonstrate that chronic visceral pain is mediated synergistically by GATA1 and TET3 via a DNA-demethylation mechanism that controls p2x7r transcription in spinal dorsal horn astrocytes, and provide a potential therapeutic strategy by targeting GATA1 and p2x7r locus binding.

Progresses in processing technologies for special foods with ultra-long shelf life - Yanzhen Long; Min Zhang; Sakamon Devahastin; Ping Cao (Critical Reviews in Food Science and Nutrition, 2022)

Four new resorcinol derivatives with neuroprotective activities from Xylaria nigripes - Lan-Qing Li; Jing Li; Hong-Ping Long; Ji-Kai Liu; Xian Wang (Natural Product Research, 2022)

Research on Mechanisms and Precursors of Slip and Fracture of Coal–Rock Parting–Coal Structure - Zhi-Long He; Cai-Ping Lu; Xiu-Feng Zhang; Ying Guo; Chao Wang; Heng Zhang; Bao-Qi Wang (Rock Mechanics and Rock Engineering, 2022)

The association between environmental exposure to perchlorate, nitrate, and thiocyanate and all-cause and cause-specific mortality - Long Wang; Zhi Fu; Beibei Gao; Xuming Mo; Ping Liang; Jinyu Huang (Environmental Science and Pollution Research, 2022)

Identification and expression analysis of grape LRK10L-2 genes during grape fruit development - Jin-Ping Ma; Xue-Ren Yin; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Sheng-Di Yang; Hui-Ying Jin; Guang-Qi He; Da-Long Guo (Plant Biotechnology Reports, 2022)

SKI knockdown suppresses apoptosis and extracellular matrix degradation of nucleus pulposus cells via inhibition of the Wnt/β-catenin pathway and ameliorates disc degeneration - Zuo-long Wu; Ya-jun Chen; Guang-zhi Zhang; Qi-qi Xie; Ke-ping Wang; Xin Yang; Tai-Cong Liu; Zhi-qiang Wang; Guang-hai Zhao; Hai-Hong Zhang (Apoptosis, 2022)

Oxidation of organoarsenicals and antimonite by a novel flavin monooxygenase widely present in soil bacteria - Jun Zhang; Jian Chen; Yi‐Fei Wu; Zi‐Ping Wang; Ji‐Guo Qiu; Xiao‐Long Li; Feng Cai; Ke‐Qing Xiao; Xiao‐Xu Sun; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Arsenic can be biomethylated to form a variety of organic arsenicals differing in toxicity and environmental mobility. Trivalent methylarsenite (MAs(III)) produced in the methylation process is more toxic than inorganic arsenite (As(III)). MAs(III) also serves as a primitive antibiotic and, consequently, some environmental microorganisms have evolved mechanisms to detoxify MAs(III). However, the mechanisms of MAs(III) detoxification are not well understood. In this study, we identified an arsenic resistance ( ars ) operon consisting of three genes, arsRVK , that contribute to MAs(III) resistance in Ensifer adhaerens ST2. ArsV is annotated as an NADPH‐dependent flavin monooxygenase with unknown function. Expression of arsV in the arsenic hypersensitive Escherichia coli strain AW3110 Δars conferred resistance to MAs(III) and the ability to oxidize MAs(III) to MAs(V). In the presence of NADPH and either FAD or FMN, purified ArsV protein was able to oxidize both MAs(III) to MAs(V) and Sb(III) to Sb(V). Genes with arsV ‐like sequences are widely present in soils and environmental bacteria. Metagenomic analysis of five paddy soils showed the abundance of arsV ‐like sequences of 0.12–0.25 ppm. These results demonstrate that ArsV is a novel enzyme for the detoxification of MAs(III) and Sb(III) and the genes encoding ArsV are widely present in soil bacteria.

The Status of Silver Carp Resources and Their Complementary Mechanism in the Yangtze River - Di-an Fang; Yan-feng Zhou; Peng Ren; Yun-xing Peng; Xiang-ping Xue; Long Ren; Dong-po Xu (Frontiers in Marine Science, 2022)
The global climate and environmental variability can induce fish adaptive strategy change and form a corresponding complementary mechanism subsequently. Because of climate fluctuation, human activities, and water conservancy projects, it has been reported that natural fish resources of the silver carp have been declining in a wavy trend from 1950. However, few studies have explored the potential effects of determining the relationship between the adult fish and fish larvae. Using the field survey method, this study analyzed the fisheries resource status of the adult silver carp and its early life stage in the Yangtze River. Results indicated that different geographic populations showed significant habitat dependence, and the adult silver carp tends to choose habitats with slow water flow, rich biological bait, and less human interference. What is more, its distribution pattern has regional and seasonal differences obviously. Additionally, redundancy analysis on the fish larvae showed that water temperature and water flow are the two most important factors influencing the fish larvae blooming. According to the generalized additive model (GAM), the hydrological factors that significantly influence the larvae abundance are water temperature, transparency, daily increasing rate of water level, and discharge ( p < 0.05). Combining the historical and present research data, the results indicated that river and lake connected habitat is essential for the silver carp recruitment and migration. Future studies should focus on the complementary mechanism of silver carp both in the natural habitat and invasion waters. It is suggested that the spawning habitat should be well protected during the channel project and economic belt construction along the Yangtze River.

Characterisation of teaghrelin-like principles from Assam tea cultivated in Thailand - Yue-Chiun Li; Chutima Tanapichatsakul; Patcharee Pripdeevech; Tsong Long Hwang; Ping-Chung Kuo; Jason T. C. Tzen (Natural Product Research, 2022)

PCSK9 mediates dyslipidemia induced by olanzapine treatment in schizophrenia patients - Jing Huang; Jingmei Xiao; Zhuang Peng; Ping Shao; Mengxi Sun; Yujun Long; Xiaoyi Wang; Manjun Shen; Dongyu Kang; Ye Yang; Xingjie Peng; Weiyan Wang; et al. (Psychopharmacology, 2022)

Seasonal variations of rotifer communities in three climatic zones: effects of environmental parameters on changes of functional groups - Fang-Ping Qian; Xin-Li Wen; Yi-Long Xi (Limnology, 2022)

Correction to: MicroRNA-351 Promotes the Proliferation and Invasion of Glioma Cells Through Downregulation of NAIF1 - Xuanxuan Wu; Chongling Hu; Chunxi Long; Xuan Zhai; Ping Liang; Zengpeng Yu (Journal of Molecular Neuroscience, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Bacterial Community Structure and Diversity in the Aqueous Environment of Shihou Lake and its Relationship with Environmental Factors - Ru Deng; Xi Chen; Li-Ping Qiu; Jia-Zhang Chen; Shun-Long Meng (Indian Journal of Microbiology, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Developments in Biological Mechanisms and Treatments for Negative Symptoms and Cognitive Dysfunction of Schizophrenia - Qiongqiong Wu; Xiaoyi Wang; Ying Wang; Yu-Jun Long; Jing-Ping Zhao; Ren-Rong Wu (Neuroscience Bulletin, 2021)
The causal mechanisms and treatment for the negative symptoms and cognitive dysfunction in schizophrenia are the main issues attracting the attention of psychiatrists over the last decade. The first part of this review summarizes the pathogenesis of schizophrenia, especially the negative symptoms and cognitive dysfunction from the perspectives of genetics and epigenetics. The second part describes the novel medications and several advanced physical therapies (e.g., transcranial magnetic stimulation and transcranial direct current stimulation) for the negative symptoms and cognitive dysfunction that will optimize the therapeutic strategy for patients with schizophrenia in future.

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

Antifungal activities and the mechanisms of biocontrol agent WE-3 against postharvest sour rot in citrus - Zhonghuan Tian; Yang Li; Qian Yang; Ping Liu; Yujie Du; Chuanwu Chen; Chao-an Long (European Journal of Plant Pathology, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Ding Wang; Ping Zhao; Rui Xiang; Shuran He; Yanli Zhou; Xinhua Yin; Guangqiang Long (Plant and Soil, 2021)

Rhizobium flavescens sp. nov., Isolated from a Chlorothalonil-Contaminated Soil - Xiao-Jing Su; Gui-Ping Liu; Long Zhang; Xi-Yi Zhou; Wen-Jing Qiao; Jian-Dong Jiang (Current Microbiology, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Improving generation of H2O2 and •OH at copper hexacyanocobaltate/graphene/ITO composite electrode for degradation of levofloxacin in photo-electro-Fenton process - Xiao-Yuan Lv; Guan-Ping Jin; Ding-Kun Yuan; Yan-Feng Ding; Peng-Xing Long (Environmental Science and Pollution Research, 2021)

Exploring soil erosion trajectories and their divergent responses to driving factors: a model-based contrasting study in highly eroded mountain areas - Chong Jiang; Zhiyuan Yang; Minting Li; Jialing Dai; Xinchi Wang; Haiyan Zhang; Long Yang; Lingling Zhao; Meili Wen; Ping Zhou (Environmental Science and Pollution Research, 2021)

Triterpenoids and steroids from the fruiting bodies of Hexagonia tenuis and their cytotoxicity - Do Xuan Hung; Ping-Chung Kuo; Nguyen Ngoc Tuan; Hoang Van Trung; Nguyen Tan Thanh; Nguyen Thi Ha; Bach Long Giang; Nguyen Quang Trung; Nguyen Thi Ngan; Ha Viet Hai; Doan Lan Phuong; Dang Ngoc Quang; et al. (Natural Product Research, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

A new dimeric protoberberine alkaloid and other compounds from the tubers of Tinospora dentata - Sio-Hong Lam; Shu-Duan Jian; Tsong-Long Hwang; Po-Jen Chen; Hsin-Yi Hung; Ping-Chung Kuo; Tian-Shung Wu (Natural Product Research, 2021)

Changes in the North Pacific subtropical gyre under 1.5 °C low warming scenario - Wen-Shan Ju; Shang-Min Long; Shang-Ping Xie; Guihua Wang; Yan Du (Climate Dynamics, 2020)

NC10 bacteria promoted methane oxidation coupled to chlorate reduction - Zi-Yan Li; Xin Li; Bin Tan; Pan-Long Lv; He-Ping Zhao (Biodegradation, 2020)

A near-infrared spectroscopy-based end-point determination method for the blending process of Dahuang soda tablets - Si-jun Wu; Ping Qiu; Pian Li; Zheng Li; Wen-long Li (Journal of Zhejiang University-SCIENCE B, 2020)

Molecularly Imprinted Polymers Doped with Carbon Nanotube with Aid of Metal-Organic Gel for Drug Delivery Systems - Long Zhao; Mei-Hong Chai; Hong-Fei Yao; Yan-Ping Huang; Zhao-Sheng Liu (Pharmaceutical Research, 2020)

Correction to: MicroRNA-351 Promotes the Proliferation and Invasion of Glioma Cells through Downregulation of NAIF1 - Xuanxuan Wu; Chongling Hu; Chunxi Long; Xuan Zhai; Ping Liang; Zengpeng Yu (Journal of Molecular Neuroscience, 2020)

MicroRNA-351 Promotes the Proliferation and Invasion of Glioma Cells through Downregulation of NAIF1 - Xuanxuan Wu; Chongling Hu; Chunxi Long; Xuan Zhai; Ping Liang; Zengpeng Yu (Journal of Molecular Neuroscience, 2020)

Integrated biomarker parameters response to the toxic effects of high stocking density, CuSO4, and trichlorfon on fish and protective role mediated by Angelica sinensis extract - HuaTao Li; YuTing Ma; Ying Liu; Min Wu; Jiao Long; XiaoQin Jing; SiShun Zhou; Ping Yuan; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Land subsidence monitoring in sinking coastal areas using distributed fiber optic sensing: a case study - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Ji-Long Yang; Song Zhang; Peng Yang (Natural Hazards, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Paleoproterozoic A-type granite from the southwestern margin of the North China block: high temperature melting of tonalitic crust in extensional setting - Xing-Ying Wang; Jiang-Feng Qin; Shao-Cong Lai; Xiao-Ping Long; Yin-Juan Ju; Ze-Zhong Zhang; Ren-Zhi Zhu (International Geology Review, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Petrogenesis and Geodynamic Implications of the Carboniferous Granitoids in the Dananhu Belt, Eastern Tianshan Orogenic Belt - Long Du; Chao Yuan; Xu-Ping Li; Yunying Zhang; Zongying Huang; Xiaoping Long (Journal of Earth Science, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Effect of the mean flow on the anomalous anticyclone over the Indo-Northwest Pacific in post-El Niño summers - Kaiming Hu; Gang Huang; Shang-Ping Xie; Shang-Min Long (Climate Dynamics, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Expression of Ihh signaling pathway in condylar cartilage after bite-raising in adult rats - Hui-qing Long; Peng-fei Tian; Yu-xin Guan; Ling-xia Liu; Xiu-ping Wu; Bing Li (Journal of Molecular Histology, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Two new species of Clavulina (Cantharellales) from southwestern China based on morphological and molecular evidence - Cheng-Long Wu; Ya He; Jun Yan; Ping Zhang (Mycological Progress, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Crop diversity facilitates soil aggregation in relation to soil microbial community composition driven by intercropping - Xiu-li Tian; Cheng-bao Wang; Xing-guo Bao; Ping Wang; Xiao-fei Li; Si-cun Yang; Guo-chun Ding; Peter Christie; Long Li (Plant and Soil, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

The effects of ethoxyquin and Angelica sinensis extracts on lipid oxidation in fish feeds and growth, digestive and absorptive capacities and antioxidant status in juvenile red carp (Cyprinus carpio var. xingguonensis): a comparative study - HuaTao Li; SiYi Tang; WenHao Du; Jun Jiang; PeiYuan Peng; Ping Yuan; YiHong Liao; Jiao Long; SiShun Zhou (Fish Physiology and Biochemistry, 2019)

Rhizobium album sp. nov., isolated from a propanil-contaminated soil - Ping Hang; Long Zhang; Xi-Yi Zhou; Qiang Hu; Jian-Dong Jiang (Antonie van Leeuwenhoek, 2019)

Calcium-dependent protein kinase CPK9 negatively functions in stomatal abscisic acid signaling by regulating ion channel activity in Arabidopsis - Dong-Hua Chen; Hui-Ping Liu; Chun-Long Li (Plant Molecular Biology, 2019)

Morphological analysis of the foramen magnum in finless porpoise (genus Neophocaena ) using postmortem computed tomography 3D volume rendered images - Brian Chin Wing Kot; Derek Kam Ping Chan; Adams Hei Long Yuen; Francis Ho Man Wong; Henry Chun Lok Tsui (Marine Mammal Science, 2019)

Cytotoxic indole alkaloids from Nauclea orientalis - Yan-Ping Liu; Peng-Kun Ju; Jin-Tao Long; Liang Lai; Wan-Hui Zhao; Chao Zhang; Zhi-Jie Zhang; Yan-Hui Fu (Natural Product Research, 2018)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

Model tests on thermo-mechanical behavior of an improved energy pile - Han-long Liu; Cheng-long Wang; Gang-qiang Kong; Charles W.W. Ng; Ping Che (European Journal of Environmental and Civil Engineering, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

Species composition, functional and phylogenetic distances correlate with success of invasive Chromolaena odorata in an experimental test - Yu‐Long Zheng; Jean H. Burns; Zhi‐Yong Liao; Yang‐ping Li; Jie Yang; Ya‐jun Chen; Jiao‐lin Zhang; Yu‐guo Zheng (Ecology Letters, 2018)
Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata , an invasive species in tropical and subtropical areas, as a measure of ‘invasion success’ in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non‐native range). We found strong evidence of biotic resistance: species richness and community biomass were negatively related with invasion success; invader biomass was greater in plant communities from China than from Mexico. Harvesting time had a greater effect on invasion success in plant communities from China than on those from Mexico. Functional and phylogenetic distances both correlated with invasion success and more functionally distant communities were more easily invaded. The effects of plant‐soil fungi and plant allelochemical interactions on invasion success were species‐specific.

Chemical constituents from Canarium album Raeusch and their anti-influenza A virus activities - Luo-Ping Yang; Xiao-Long Gu; Jin-Xiang Chen; Jie Yang; Sui-Yi Tan; Wen-Jun Duan (Journal of Natural Medicines, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Three new cassane diterpenes from the seeds of Caesalpinia minax Hance - Qin Liu; Bai Bai; De-po Yang; Shi-yi Peng; Long-ping Zhu; Mai-hui Luo; Zhi-min Zhao (Natural Product Research, 2018)

PGL3 is required for chlorophyll synthesis and impacts leaf senescence in rice - Jing Ye; Yao-long Yang; Xing-hua Wei; Xiao-jun Niu; Shan Wang; Qun Xu; Xiao-ping Yuan; Han-yong Yu; Yi-ping Wang; Yue Feng; Shu Wang (Journal of Zhejiang University-SCIENCE B, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Source-sink landscape spatial characteristics and effect on non-point source pollution in a small catchment of the Three Gorge Reservoir Region - Jin-liang Wang; Jiu-pai Ni; Cheng-long Chen; De-ti Xie; Jing-an Shao; Fang-xin Chen; Ping Lei (Journal of Mountain Science, 2018)

The role of complementarity and selection effects in P acquisition of intercropping systems - Xiao-Fei Li; Cheng-Bao Wang; Wei-Ping Zhang; Le-Hua Wang; Xiu-Li Tian; Si-Cun Yang; Wan-Li Jiang; Jasper van Ruijven; Long Li (Plant and Soil, 2018)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

The association between prognosis of breast cancer and first-degree family history of breast or ovarian cancer: a systematic review and meta-analysis - Jun-Long Song; Chuang Chen; Jing-Ping Yuan; Sheng-Rong Sun (Familial Cancer, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

Sr-Nd-Pb isotopic compositions of the lower crust beneath northern Tarim: insights from igneous rocks in the Kuluketage area, NW China - Yan Zhang; Xun Wei; Yi-Gang Xu; Xiao-Ping Long; Xue-Fa Shi; Jian-Xin Zhao; Yue-Xing Feng (Mineralogy and Petrology, 2017)

Koumine exhibits anxiolytic properties without inducing adverse neurological effects on functional observation battery, open-field and Vogel conflict tests in rodents - Chao-Jie Chen; Zhi-Feng Zhong; Zhi-Ming Xin; Long-Hui Hong; Yan-Ping Su; Chang-Xi Yu (Journal of Natural Medicines, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Constituents from the leaves of Clausena lansium and their anti-inflammatory activity - De-Yang Shen; Ping-Chung Kuo; Shiow-Chyn Huang; Tsong-Long Hwang; Yu-Yi Chan; Po-Chuen Shieh; Nguyen Thi Ngan; Tran Dinh Thang; Tian-Shung Wu (Journal of Natural Medicines, 2017)

iTRAQ-Based Comparative Proteomics Analysis of the Fruiting Dikaryon and the Non-fruiting Monokaryon of Flammulina velutipes - Jing-Yu Liu; Ming-chang Chang; Jun-long Meng; Cui-ping Feng; Yong-nan Liu (Current Microbiology, 2017)

Risk assessment and vertical distribution of thallium in paddy soils and uptake in rice plants irrigated with acid mine drainage - Xuexia Huang; Ning Li; Qihang Wu; Jianyou Long; Dinggui Luo; Ping Zhang; Yan Yao; Xiaowu Huang; Dongmei Li; Yayin Lu; Jianfeng Liang (Environmental Science and Pollution Research, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Transcriptome profiling indicating canine parvovirus type 2a as a potential immune activator - Xu-Xu Fan; Yuan Gao; Long Shu; Yan-Quan Wei; Xue-Ping Yao; Sui-Zhong Cao; Guang-Neng Peng; Xiang-Tao Liu; Shi-Qi Sun (Virus Genes, 2016)

Hypoxia-induced resistance to cisplatin-mediated apoptosis in osteosarcoma cells is reversed by gambogic acid independently of HIF-1α - Wei Zhao; Shi-Qi Xia; Jin-Peng Zhuang; Zhi-Peng Zhang; Chang-Cheng You; Jing-Long Yan; Gong-Ping Xu (Molecular and Cellular Biochemistry, 2016)

Chain elongation analog of resveratrol as potent cancer chemoprevention agent - Yan-Fei Kang; Hai-Xia Qiao; Long-Zuo Xin; Li-Ping Ge (Journal of Physiology and Biochemistry, 2016)

Simulation of Water Quality under Different Reservoir Regulation Scenarios in the Tidal River - Tao Jiang; Ming Zhong; Ying-jie Cao; Long-jian Zou; Bo Lin; Ai-ping Zhu (Water Resources Management, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Two new glycosides isolated from Sapindus mukorossi fruits: effects on cell apoptosis and caspase-3 activation in human lung carcinoma cells - Xuan-Ming Zhang; De-Po Yang; Zhi-Yong Xie; Qing Li; Long-Ping Zhu; Zhi-Min Zhao (Natural Product Research, 2016)

High-resolution genetic linkage mapping, high-temperature tolerance and growth-related quantitative trait locus (QTL) identification in Marsupenaeus japonicus - Xia Lu; Sheng Luan; Long Yang Hu; Yong Mao; Ye Tao; Sheng Ping Zhong; Jie Kong (Molecular Genetics and Genomics, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Prediction of drug-induced eosinophilia adverse effect by using SVM and naïve Bayesian approaches - Hui Zhang; Peng Yu; Ming-Li Xiang; Xi-Bo Li; Wei-Bao Kong; Jun-Yi Ma; Jun-Long Wang; Jin-Ping Zhang; Ji Zhang (Medical & Biological Engineering & Computing, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Anthropogenic activities drive the microbial community and its function in urban river sediment - Xu Zhang; Qing Gu; Xi-En Long; Zhao-Lei Li; Dong-Xiu Liu; Dan-Hua Ye; Chi-Quan He; Xiao-Yan Liu; Kristiina Väänänen; Xue-Ping Chen (Journal of Soils and Sediments, 2016)

Spatial driving forces of dominant land use/land cover transformations in the Dongjiang River watershed, Southern China - Changjun Gao; Ping Zhou; Peng Jia; Zhiyong Liu; Long Wei; Huiling Tian (Environmental Monitoring and Assessment, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Gas desorption index of drill cuttings affected by magmatic sills for predicting outbursts in coal seams - Long-biao Cheng; Liang Wang; Yuan-ping Cheng; Kan Jin; Wei Zhao; Li-shuo Sun (Arabian Journal of Geosciences, 2016)

High morphological and physiological plasticity of wheat roots is conducive to higher competitive ability of wheat than maize in intercropping systems - Yi-Xiang Liu; Wei-Ping Zhang; Jian-Hao Sun; Xiao-Fei Li; Peter Christie; Long Li (Plant and Soil, 2015)

Growth trajectories and interspecific competitive dynamics in wheat/maize and barley/maize intercropping - Wei-Ping Zhang; Guang-Cai Liu; Jian-Hao Sun; Li-Zhen Zhang; Jacob Weiner; Long Li (Plant and Soil, 2015)

Preventive effects of phenylethanol glycosides from Cistanche tubulosa on bovine serum albumin-induced hepatic fibrosis in rats - Shu-Ping You; Jun Zhao; Long Ma; Mukaram Tudimat; Shi-Lei Zhang; Tao Liu (DARU Journal of Pharmaceutical Sciences, 2015)

Effects of Multi-metal (Cu, Zn, Cd, Cr, and Mn) Mixtures on the Reproduction of Freshwater Rotifer Brachionus calyciflorus - Xiao-Ping Xu; Yi-Long Xi; Lin Huang; Xian-Ling Xiang (Bulletin of Environmental Contamination and Toxicology, 2015)

Flavobacterium buctense sp. nov., isolated from freshwater - Xiao-Min Feng; Xu Tan; Li Jia; Ping-Ping Long; Lu Han; Jie Lv (Archives of Microbiology, 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Full magnetic gradient tensor from triaxial aeromagnetic gradient measurements: Calculation and application - Yao Luo; Mei-Ping Wu; Ping Wang; Shu-Ling Duan; Hao-Jun Liu; Jin-Long Wang; Zhan-Feng An (Applied Geophysics, 2015)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Restoring ecosystem services to littoral zones of rivers in the urban core of Chongqing, China - Xu-Dong Xian; Yi-Long Feng; J. H. Martin Willison; Li-Jiao Ai; Ping Wang; Zhi-Neng Wu (Environmental Science and Pollution Research, 2015)

N2O emissions from banana plantations in tropical China as affected by the application rates of urea and a urease/nitrification inhibitor - Tongbin Zhu; Junhua Zhang; Ping Huang; Long Suo; Cong Wang; Weixin Ding; Lei Meng; Kexin Zhou; Zhewei Hu (Biology and Fertility of Soils, 2015)

Two new macrosporin dimers from the fungus Alternaria sp. XZSBG-1 - Bin Chen; Lan Liu; Xun Zhu; Jun Wang; Yi Long; Si-Ping Jiang; Ai-Guo Xu; Yong-Cheng Lin (Natural Product Research, 2015)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Association between PPAR-γ2 Pro12Ala polymorphism and obesity: a meta-analysis - Ying-shui Yao; Jie Li; Yue-long Jin; Yan Chen; Lian-ping He (Molecular Biology Reports, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Correlation of an interleukin-4 gene polymorphism with susceptibility to severe enterovirus 71 infection in Chinese children - Fei Li; Xiang-ping Liu; Ji-an Li; Zhen-liang Han; Pei-pei Liu; Yuan-yuan Wang; Long Song; Zong-bo Chen (Archives of Virology, 2015)

Research of CRP-based irregular 2D seismic acquisition - Hu Zhao; Cheng Yin; Guang-Ming He; Ai-Ping Chen; Long-Jiang Jing (Applied Geophysics, 2015)

A nonlinear statistical ensemble model for short-range rainfall prediction - Long Jin; Jieshun Zhu; Ying Huang; Hua-sheng Zhao; Kai-ping Lin; Jian Jin (Theoretical and Applied Climatology, 2015)

Identification of QTLs associated with salt or alkaline tolerance at the seedling stage in rice under salt or alkaline stress - Jing-long Liang; Ying-ping Qu; Chun-gang Yang; Xiao-ding Ma; Gui-lan Cao; Zheng-wu Zhao; San-yuan Zhang; Tao Zhang; Long-zhi Han (Euphytica, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Characterization of a glutamine synthetase gene BnGS1-2 from ramie (Boehmeria nivea L. Gaud) and biochemical assays of BnGS1-2-over-expressing transgenic tobacco - Jian-Shu Zheng; Chun-Ming Yu; Ping Chen; Yan-Zhou Wang; Long-Tao Tan; Ji-Kang Chen; He-Ping Xiong (Acta Physiologiae Plantarum, 2015)

Cloning and respond of a cold shock domain protein (CnCSDP) gene to cold stress in noble scallop Chlamys nobilis (Bivalve: Pectinidae) - Ya-Jun Wang; Huai-Ping Zheng; Bo Zhang; He-Lu Liu; Hua-Juan Deng; Long-Hui Deng (Molecular Biology Reports, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Molecular characterization of an infectious bronchitis virus strain isolated from northern China in 2012 - Ye Zhao; Xiao-yu Liu; Jin-long Cheng; Yan-ping Wu; Guo-zhong Zhang (Archives of Virology, 2014)

Mitochondrial genomes of domestic animals need scrutiny - Ni‐Ni Shi; Long Fan; Yong‐Gang Yao; Min‐Sheng Peng; Ya‐Ping Zhang (Molecular Ecology, 2014)
More than 1000 complete or near‐complete mitochondrial DNA (mt DNA ) sequences have been deposited in GenBank for eight common domestic animals (cattle, dog, goat, horse, pig, sheep, yak and chicken) and their close wild ancestors or relatives, as well. Nevertheless, few efforts have been performed to evaluate the sequence data quality. Herein, we conducted a phylogenetic survey of these complete or near‐complete mt DNA sequences based on mt DNA haplogroup trees for the eight animals. We show that errors due to artificial recombination, surplus of mutations and phantom mutations do exist in 14.5% (194/1342) of mt DNA sequences and all of them should be treated with wide caution. We propose some caveats for future mt DNA studies of domestic animals.

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Variation in β-amylase activity and thermostability in Tibetan annual wild and cultivated barley genotypes - Hai-tao Zhang; Tian-long Chen; Bing-lin Zhang; De-zhi Wu; Ye-chang Huang; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Neuroprotective effect of schizandrin A on oxygen and glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons - Cai-Ping Wang; Gui-Cai Li; Yun-Wei Shi; Xiao-Chuan Zhang; Jian-Long Li; Zhi-Wei Wang; Fei Ding; Xin-Miao Liang (Journal of Physiology and Biochemistry, 2014)

Axinelline A, a new COX-2 inhibitor from Streptomyces axinellae SCSIO02208 - Wen Ai; Xiu-Ping Lin; Zhengchao Tu; Xin-Peng Tian; Xin Lu; Fredimoses Mangaladoss; Zhi-Long Zhong; Yonghong Liu (Natural Product Research, 2014)

The Life-Table Demographic Response of Freshwater Rotifer Brachionus calyciflorus to Multi-metal (Cu, Zn, Cd, Cr, and Mn) Mixture Interaction - Xiao-Ping Xu; Yi-Long Xi; Lin Huang; Xian-Ling Xiang (Bulletin of Environmental Contamination and Toxicology, 2014)

Isolation and characterization of phosphate-solubilizing bacteria from betel nut (Areca catechu) and their effects on plant growth and phosphorus mobilization in tropical soils - Fu-Ping Liu; Hai-Qing Liu; Hai-Long Zhou; Zhi-Guo Dong; Xu-Hao Bai; Peng Bai; Jian-Jun Qiao (Biology and Fertility of Soils, 2014)

A new triterpenoid saponin and an oligosaccharide isolated from the fruits of Sapindus mukorossi - Xuan-Ming Zhang; De-Po Yang; Zhi-Yong Xie; Xue Xue; Long-Ping Zhu; Dong-Mei Wang; Zhi-Min Zhao (Natural Product Research, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Positive matrix factorization as source apportionment of soil lead and cadmium around a battery plant (Changxing County, China) - Jian-long Xue; Yu-you Zhi; Li-ping Yang; Jia-chun Shi; Ling-zao Zeng; Lao-sheng Wu (Environmental Science and Pollution Research, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Eliminating host-mediated effects demonstrates Bt maize producing Cry1F has no adverse effects on the parasitoid Cotesia marginiventris - Jun-Ce Tian; Xiang-Ping Wang; Li-Ping Long; Jörg Romeis; Steven E. Naranjo; Richard L. Hellmich; Anthony M. Shelton (Transgenic Research, 2014)

Thermal effects of magmatic sills on coal seam metamorphism and gas occurrence - Liang Wang; Long-biao Cheng; Yuan-ping Cheng; Guang-zhi Yin; Chun-cheng Cai; Chao Xu; Kan Jin (Bulletin of Volcanology, 2014)

Anchored periplasmic expression (APEx)-based bacterial display for rapid and high-throughput screening of B cell epitopes - Mo Guo; Li-Ming Xu; Bing Zhou; Jie-Chao Yin; Xian-Long Ye; Gui-Ping Ren; De-Shan Li (Biotechnology Letters, 2014)

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase - Ping-Lin Ong; Tzu-Ting Chuang; Tzu-Fan Wang; Long-Liu Lin (Biologia, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Investigation of individual heterozygosity correlated to growth traits in Tongshan Black-boned goat - Yan Guo Han; Gui Qiong Liu; Xun Ping Jiang; Guo Ming Liang; Chun Bo He; Dang Wei Wang; Yan Wu; Xing Long Xiang; Jie Hu; Yu Qin Peng (Molecular Biology Reports, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Viability inhibition effect of gambogic acid combined with cisplatin on osteosarcoma cells via mitochondria-independent apoptotic pathway - Wei Zhao; Chang-Cheng You; Jin-Peng Zhuang; Jia-Ning Zu; Zhi-Yong Chi; Gong-Ping Xu; Jing-Long Yan (Molecular and Cellular Biochemistry, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Diversity arrays technology (DArT) for studying the genetic polymorphism of flue-cured tobacco (Nicotiana tabacum) - Xiu-ping Lu; Bing-guang Xiao; Yong-ping Li; Yi-jie Gui; Yu Wang; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2013)

1H-MRS Assessment of the Therapeutic Effect of Bilateral Intraventricular BDNF Infusion into APP/PS1 Double Transgenic Mice - Wei Zhang; Pei-jun Wang; Ming-hua Li; Guo-liang Wang; Ping Li; Xiao-long Gao (Journal of Molecular Neuroscience, 2013)

A conserved region in the 3′ untranslated region of the human LIMK1 gene is critical for proper expression of LIMK1 at the post-transcriptional level - Guang-Fei Deng; Shu-Jing Liu; Xun-Sha Sun; Wei-Wen Sun; Qi-Hua Zhao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Neuroscience Bulletin, 2013)

Detection of African swine fever virus-like sequences in ponds in the Mississippi Delta through metagenomic sequencing - Xiu-Feng Wan; J. Lamar Barnett; Fred Cunningham; Si Chen; Guohua Yang; Shannon Nash; Li-Ping Long; Lorelei Ford; Sherry Blackmon; Yan Zhang; Larry Hanson; Qiang He (Virus Genes, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Time lag between carbon dioxide influx to and efflux from bare saline-alkali soil detected by the explicit partitioning and reconciling of soil CO2 flux - Xi Chen; Wen-Feng Wang; Ge-Ping Luo; Long-Hui Li; Yan Li (Stochastic Environmental Research and Risk Assessment, 2013)

Analysis of selected singleton transposable elements (SSTEs) and their application for the development of land PATE markers in Magnaporthe oryzae - Hong-yan Zhang; Dong-yang He; Teerapong Kasetsomboon; Heng Zhou; Ping Li; Xiang-long Li; Chatchawan Jantasuriyarat; Bo Zhou (Journal of General Plant Pathology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Protein domains, catalytic activity, and subcellular distribution of mouse NTE-related esterase - Ping’an Chang; Zhan-xiang Wang; Dingxin Long; Wenzhen Qin; Yijun Wu (Molecular and Cellular Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

No evidence for evolutionarily decreased tolerance and increased fitness in invasive Chromolaena odorata: implications for invasiveness and biological control - Yang-Ping Li; Yu-Long Feng; Gregor Barclay (Plant Ecology, 2012)

Degradation of mouse NTE-related esterase by macroautophagy and the proteasome - Ping-An Chang; Yu-Ying Chen; Ding-Xin Long; Wen-Zhen Qin; Xiao-Ling Mou (Molecular Biology Reports, 2012)

Quercetin modulates activities of Taiwan cobra phospholipase A2 via its effects on membrane structure and membrane-bound mode of phospholipase A2 - Yi-Ling Chiou; Shinne-Ren Lin; Wan-Ping Hu; Long-Sen Chang (Journal of Biosciences, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Response of Sulfide:Quinone Oxidoreductase to Sulfide Exposure in the Echiuran Worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Xiao-Li Shi; Ying-Ping Dong; Jin-Long Li (Marine Biotechnology, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

A Lipoxin A4 Analog Ameliorates Blood–Brain Barrier Dysfunction and Reduces MMP-9 Expression in a Rat Model of Focal Cerebral Ischemia–Reperfusion Injury - Yan Wu; Yan-Ping Wang; Peipei Guo; Xi-Hong Ye; Jie Wang; Shi-Ying Yuan; Shang-Long Yao; You Shang (Journal of Molecular Neuroscience, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Genetic structure of three fosmid‐fragments encoding 16S rRNA genes of the Miscellaneous Crenarchaeotic Group (MCG): implications for physiology and evolution of marine sedimentary archaea - Ping‐Yi Li; Bin‐Bin Xie; Xi‐Ying Zhang; Qi‐Long Qin; Hong‐Yue Dang; Xu‐Min Wang; Xiu‐Lan Chen; Jun Yu; Yu‐Zhong Zhang (Environmental Microbiology, 2012)
Summary Archaea of the Miscellaneous Crenarchaeotic Group (MCG) exist widely in soil, freshwater and marine sediments of both surface and subsurface. However, current knowledge about this group is limited to its phylogenetic diversity. An archaeal 16S library was constructed from a sediment sample from the South China Sea, which was dominated by MCG and Marine Group I (MG‐I). A metagenomic library was constructed from the same sediment sample, and three MCG fosmids (E6‐3G, E37‐7F and E48‐1C) containing 16S rRNA genes were screened. Annotation showed that the three genomic fragments encode a variety of open reading frames (ORFs) that are potentially homologous to important functional genes related to lipid biosynthesis, energy metabolism, and resistance to oxidants. No colinear regions were found between MCG fosmids and reported archaeal genomic fragments or genomes, suggesting that the MCG archaea are quite different from the sequenced archaea in gene arrangement. Analyses of both the phylogenies of 16S rRNA genes and several informational processing genes and nucleotide frequencies showed that MCG archaea are distinct from MG‐I plus relatives. In addition, tetranucleotide frequency analysis in combination with phylogenetic analysis suggested that some fragments in the MCG fosmids are probably derived from non‐MCG or non‐archaeal genomes.

Innate and evolutionarily increased advantages of invasive Eupatorium adenophorum over native E. japonicum under ambient and doubled atmospheric CO2 concentrations - Yan Bao Lei; Yu Long Feng; Yu Long Zheng; Rui Fang Wang; He De Gong; Yi Ping Zhang (Biological Invasions, 2011)

Induction of hairy roots and plant regeneration from the medicinal plant Pogostemon Cablin - Shi He-Ping; Long Yong-Yue; Sun Tie-Shan; Tsang Po Keung Eric (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Spatial and temporal variations of nitrogen pollution in Wen-Rui Tang River watershed, Zhejiang, China - Ping Lu; Kun Mei; Yujin Zhang; Lingling Liao; Bibo Long; Randy A. Dahlgren; Minghua Zhang (Environmental Monitoring and Assessment, 2011)

Identification of the transcriptional promoters in the proximal regions of human microRNA genes - Yue-Sheng Long; Guang-Fei Deng; Xun-Sha Sun; Yong-Hong Yi; Tao Su; Qi-Hua Zhao; Wei-Ping Liao (Molecular Biology Reports, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Genotype-phenotype correlations in Chinese patients with TGFBI gene-linked corneal dystrophy - Yan Long; Yang-shun Gu; Wei Han; Xiu-yi Li; Ping Yu; Ming Qi (Journal of Zhejiang University-SCIENCE B, 2011)

Comparative analysis of rotifer community structure in five subtropical shallow lakes in East China: role of physical and chemical conditions - Xin-Li Wen; Yi-Long Xi; Fang-Ping Qian; Gen Zhang; Xian-Ling Xiang (Hydrobiologia, 2011)

The role of cell cycle-dependent neuropathy target esterase in cell proliferation - Ping-An Chang; Yu-ying Chen; Wen-zhen Qin; Ding-Xin Long; Yi-Jun Wu (Molecular Biology Reports, 2011)

Construction and characterization of a full-length infectious clone from a fast-replicating, X4-tropic HIV-1 subtype B′ isolate - Shou-li Wu; Yan-sheng Yan; Ping-ping Yan; Hai-long Huang; Hui-rong Wang (Archives of Virology, 2010)

Identification of novel cyclic nucleotide phosphodiesterase gene cDNAs in the brain of guinea pig - Yue-Sheng Long; Min-Qi Huang; Wei-Ping Liao (Neuroscience Bulletin, 2010)

Eleven polymorphic microsatellite loci in Polygonatum filipes and cross-amplification in other congeneric species - Ting-ting Liu; Wen-juan Cheng; Shou-biao Zhou; Jian-wen Shao; Hai-long Wu; Guo-ping Zhu (Conservation Genetics Resources, 2010)

Isolation and characterization of twelve polymorphic microsatellite loci in Polygonatum cyrtonema and cross-species amplification - Wen-juan Cheng; Ting-ting Liu; Hai-long Wu; Shou-biao Zhou; Shou-qin Xuan; Guo-ping Zhu (Conservation Genetics Resources, 2010)

Protein domains, catalytic activity, and subcellular distribution of mouse NTE-related esterase - Ping-an Chang; Zhan-xiang Wang; Ding-xin Long; Wen-zhen Qin; Yi-jun Wu (Molecular and Cellular Biochemistry, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

BMP-2/PLGA Delayed-Release Microspheres Composite Graft, Selection of Bone Particulate Diameters, and Prevention of Aseptic Inflammation for Bone Tissue Engineering - Ye Ji; Gong ping Xu; Zhi peng Zhang; Jing jun Xia; Jing long Yan; Shang ha Pan (Annals of Biomedical Engineering, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Isolation and characterization of fifteen polymorphic microsatellite loci from Primula merrilliana (Primulaceae), an endemic from China - Yan-qiu Peng; Jian-wen Shao; Hai-long Wu; Xiao-ping Zhang; Guo-ping Zhu (Conservation Genetics, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

The complete nucleotide sequence of the mitochondrial genome of Phthonandria atrilineata (Lepidoptera: Geometridae) - Ling Yang; Zhao-Jun Wei; Gui-Yun Hong; Shao-Tong Jiang; Long-Ping Wen (Molecular Biology Reports, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Study on swelling model and thermodynamic structure of native konjac glucomannan - Long Li; Hui Ruan; Liu-liu Ma; Wei Wang; Ping Zhou; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2009)

Limestone Dissolution Induced by Fungal Mycelia, Acidic Materials, and Carbonic Anhydrase from Fungi - Wei Li; Peng-Peng Zhou; Li-Ping Jia; Long-Jiang Yu; Xue-Li Li; Min Zhu (Mycopathologia, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Analysis of synonymous codon usage and evolution of begomoviruses - Xiao-zhong Xu; Qing-po Liu; Long-jiang Fan; Xiao-feng Cui; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Molecular cloning and expression of the C-terminal domain of mouse NTE-related esterase - Ping-An Chang; Ding-Xin Long; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Through the genetic bottleneck: O. rufipogon as a source of trait-enhancing alleles for O. sativa - Susan R. McCouch; Megan Sweeney; Jiming Li; Hui Jiang; Michael Thomson; Endang Septiningsih; Jeremy Edwards; Pilar Moncada; Jinhua Xiao; Amanda Garris; Tom Tai; Cesar Martinez; et al. (Euphytica, 2007)

Trace Measurement of Phenothiazine Drugs in Tablets by Micellar-Enhanced Fluorophotometric Method - Gong-Jun Yang; Xi-Long Qu; Ming Shen; Qi-Shu Qu; Chen-Ying Wang; Ai-Ping Zhu; Xiao-Ya Hu (Journal of Fluorescence, 2007)

QTL mapping for economic traits based on a dense genetic map of cotton with PCR-based markers using the interspecific cross of Gossypium hirsutum × Gossypium barbadense - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Yan-Xin Zhang; Wu Li (Euphytica, 2007)

Effect of glycine site/NMDA receptor antagonist MRZ2/576 on the conditioned place preference and locomotor activity induced by morphine in mice - Yong-ping Zhu; Zai-hao Long; Ming-lan Zheng; Ralf Binsack (Journal of Zhejiang University-SCIENCE B, 2006)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

Comparative blood biochemistry of Amur sturgeon, Acipenser schrenckii, and Chinese surgeon, Acipenser sinensis - Xiaotao Shi; Dapeng Li; Ping Zhuang; Fen Nie; Liangqi Long (Fish Physiology and Biochemistry, 2006)

Mapping QTLs of traits contributing to yield and analysis of genetic effects in tetraploid cotton - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Chun-Da Feng; James McD. Stewart (Euphytica, 2005)

Karyomorphology of Maianthemum sensu lato (Polygonatae, Ruscaceae) - Ying Meng; Ze-Long Nie; Yong-Ping Yang; Zhi-Jian Gu (Journal of Plant Research, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Overexpression of the AP2/EREBP transcription factor OPBP1 enhances disease resistance and salt tolerance in tobacco - Ze-Jian Guo; Xu-Jun Chen; Xue-Long Wu; Jian-Qun Ling; Ping Xu (Plant Molecular Biology, 2004)

Gene mutation of thiopurine S -methyltransferase in Uygur Chinese - Jian-Ping Zhang; Yong-Yuan Guan; An-Long Xu; Shu-Feng Zhou; Jue-Heng Wu; Hong Wei; Min Huang (European Journal of Clinical Pharmacology, 2004)

Genetic Diversity and Relationship of Yunnan Native Cattle Breeds and Introduced Beef Cattle Breeds - Ying Yu; Lin-Sheng Lian; Ji-Kun Wen; Xian-Wei Shi; Fang-Xian Zhu; Long Nie; Ya-Ping Zhang (Biochemical Genetics, 2004)

Cleavage of CD14 and LBP by a protease from Prevotella intermedia - James Deschner; Anuradha Singhal; Ping Long; Chau-Ching Liu; Nicholas Piesco; Sudha Agarwal (Archives of Microbiology, 2003)

Effects of soil fauna on litter decomposition - Xue-ping Zhang; Si-cong Zhang; Chu-long Huang (Chinese Geographical Science, 2001)

Effect of the neuroprotective agent riluzole on intracellular Ca 2+ levels in IMR32 neuroblastoma cells - Jue-Long Wang; Kam-Chung Lee; Kwong-Yui Tang; Ti Lu; Cheng-Ho Chang; Chik-Keung Chow; Wei-Chuan Chen; Warren Su; Yee-Ping Law; Chung-Ren Jan (Archives of Toxicology, 2001)

NOTE: Blood Protein Polymorphism in B. frontalis, B. grunniens, B. taurus, and B. indicus - Zheng-chao Tu; Long Nie; Ying Yu; Ji-kun Wen; Ya-ping Zhang (Biochemical Genetics, 2000)

Genetic Diversity of Cattle in South China as Revealed by Blood Protein Electrophoresis - Long Nie; Ying Yu; Xi-Quan Zhang; Guan-Fu Yang; Ji-Kun Wen; Ya-Ping Zhang (Biochemical Genetics, 1999)